Metabolic redirection and capacity expansion in heterotroph-reinforced microalgae-methanotroph systems under high ammonia stress - Yong-Ze Lu; Jia-Sen Yang; Xin-Ya Tan; Yi-Ru Wang; Hong-Yin Sha; Hao-Yu Wang; Shao-Jie Zong; Guang-Can Zhu (Bioresource Technology, 2027)

Seismic response of an offshore jacket-type HVSR station in liquefiable seabed using a modified SANISAND model - Wen-Jie Ren; Ling-Yu Xu; Dong Cai; Ye-Jun Sun; Jun Wang; Chen Wang; Zheng-Hai Sha; Feng-Xue Jin; Wei-Yun Chen (Soil Dynamics and Earthquake Engineering, 2026)

Film mulching and organic fertilizer improve soil quality and maize yield in saline-alkali soils by enhancing soil organic carbon fractions and modulating microbial community structure - Ying SHA; Yanru BU; Haiying ZONG; Fangli WANG; Jun LIU; Lei YU; Shunzhang YU; Xuexia WANG; Xiaohong GUO; Xinwei LIU; Xiangyun SONG; Ningning SONG (Soil and Tillage Research, 2026)

Postharvest control of Botryosphaeria dothidea-induced pear ring rot by Chrysanthemum indicum essential oil: Composition, efficacy, and mechanistic insights - Bin Wang; Sha-Sha Liu; Jia-Ying Wu; Meng-Ran Yu; Yun-Kai Lv; Jian Wang; Li-Juan Wang; Fei Cao (Postharvest Biology and Technology, 2026)

From sludge to sustained-release biochar-based phosphorus fertilizer: CaO-mediated phosphorus transformation, soil amelioration, and agronomic performance across contrasting soil types - Zhengkang Zou; Xiaoxiao Xu; Sha Liang; Beibei Dou; Wenbo Yu; Huabo Duan; Jiakuan Yang; Xiong Shi (Biomass and Bioenergy, 2026)

Correction to: Spil mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

Spil-mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

Precursor rigidity engineering enables synergistic regulation of closed pores and graphitic domains for balancing energy and power densities in hard carbon anodes - Qiaofeng Huang; Yiwen Sun; Haoliang Lin; Yuhai Wang; Yifan Sha; Weizhen Fan; Litao Shi; Yu Ying; Xianjian Duan; Chunlei Wu; Guang Shi (Chemical Engineering Journal, 2026)

Poly(phenol-imidazole) nanosheets engineered multifunctional hydrogel for promotion of infected diabetic wound healing - Jia Xin Yu; Lu Yao Li; Yu Fan; Piao Zheng; Sha Yang; Qi Fang Liu; Cai Juan Huang; Ya Lin Cao; Yang You (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

CRISPR/Cas9-mediated disruption of mdfi is associated with enhanced muscle growth in grass carp (Ctenopharyngodon idella) - Ruixue Zhang; Suxu Tan; Hongning Liu; Wenwen Wang; Yanzhao Nie; Lizheng Gao; Yiran Song; Xinlu Ren; Yu Yang; Hui Liu; Wenting Huang; Songlin Chen; et al. (Aquaculture, 2026)

Microplastics-induced effects on membrane fouling and effluent quality in MBRs for landfill leachate treatment under long-term operation - Shijie Bian; Jingwei Yan; Timing Jiang; Huying Li; Rui Cai; Wen Li; Jingjing Shi; Fan Yang; Sha Liang; Huabo Duan; Wenbo Yu; Shushan Yuan; et al. (Waste Management, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

Hyperspectral monitoring of wheat gluten index based on multi-model ensemble and adaptive learning - Shiyou Zhu; Juan Bai; Yulong Chen; Jingyu Chen; Caiyu Ji; Yingchao Hao; Sha Yang; Yu Zhao; Meijun Zhang; Meichen Feng; Wude Yang; Guangxin Li (Food Chemistry, 2026)

Optimizing rice yield simulation by integrating dynamic dry matter partitioning and high-temperature stress with a remote sensing-based process model - Zhiyuan Ma; Jiahua Zhang; Liming Yu; Xin Jiang; Yun Bai; Shanshan Yang; Sha Zhang; Fengmei Yao (Field Crops Research, 2026)

HYDRA-EDGE: HYDrogel-based rapid assay with entropy-driven gel enhancement for point-of-care viral detection - Ailing Yang; Li Zhou; Jing Li; Yu Liu; Ting Xiao; Qingxiang Yang; Dunquan Xu; Jiezhong Deng; Ming Chen; Sha Yang (Chemical Engineering Journal, 2026)

Vortex bionic structural composites fabricated by DLP 3D printing with high electromagnetic shielding effect and thermal conductive property - Jingxing Gui; Tao Zhang; Sha Long; Yingtao Li; Feiyue Zhou; Yuxuan Ma; Yuting Xue; Xueting Xu; Chunyan Hu; Baojiang Liu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Role of SIRT3-mediated IDH2 deacetylation in energy metabolism disorders and necroptosis of chondrocytes induced by T-2 Toxin - Fang-Fang Yu; Yan-Jie Dou; Tong-Tong Sha; Huan-Xia Zhang; Yao Li; Qian Li; Zai-Chao Dong; Guang-Ning Kou (Chemico-Biological Interactions, 2026)

Effects of metal ions and pH on the optical properties of atmospheric brown carbon - Yu Huang; Ruoyuan Lei; Yingying Sha; Haiwei Li; Yunjiang Zhang; Junfeng Wang; Yun Wu; Ming Wang; Jianhuai Ye; Xinlei Ge (Atmospheric Pollution Research, 2026)

Honokiol Ameliorates Pyroptosis in Bovine Mammary Epithelial Cells via SIRT3-Mediated Inhibition of the NLRP3 Inflammasome - Sha Tang; Yanqiong Wen; Renxin Wu; Xing Shi; Dan Li; Siqing Mao; Xiao Yang; Hang Yu; Lei Tian; Le Zhang; Lei Liu (Tissue and Cell, 2026)

Reconstructing lattice Cu2+ to surface Cu0 in CuCo spinel drives reverse charge transfer for selective peracetic acid activation toward water decontamination - Hao Chen; Quan Wang; Wenjun Gao; Sha Yu; Hongying Zhao; Yuanzhen Zhou (Journal of Hazardous Materials, 2026)

A fluorescent/photochromic dual-function Mo-based hydrogel for information encryption - Sha Long; Yanghang Liu; Jingxing Gui; Yuting Xue; Yuxuan Ma; Baojiang Liu; Chunyan Hu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Supported catalytic packing by epoxy resin porous transition layer on stainless steel for reactive distillation of ethyl acetate - Haoran Yin; Miao Yu; Yuting Wu; Mingyu Yu; Yong Sha (Chemical Engineering Journal, 2026)

An autonomous cascade for H2O2 generation, utilization, and regulation enabled by a triple-enzyme-mimicking Pt single-atom nanozyme toward dual-mode acid phosphatase detection - Kelong Yang; Junping Ma; Sha Yu; Zhihua Hou; Jing Zhang; Jun-Jie Zhu; Yuanzhen Zhou (Chemical Engineering Journal, 2026)

Blockchain adoption, pricing, and undeclaration in maritime dangerous goods transportation - Zui Xu; Mei Sha; Dayong Yu; Shuang Li; Jianli Shen; Yue Shang (Frontiers in Marine Science, 2026)
Introduction Shippers may undeclare maritime dangerous goods as general cargo to avoid the preparation time, documentation burden, and freight premium associated with dangerous goods transportation, creating serious risks for vessel safety, port operations, and the marine environment. This paper examines whether blockchain-enabled documentation can mitigate such undeclaration by improving provenance information and shortening preparation and verification time in the dangerous goods channel. Methods We develop a game-theoretic model with one carrier and a continuum of heterogeneous shippers who differ in their marginal willingness to pay for service level, and in which the carrier endogenously sets the dangerous goods transportation price. We characterize the equilibrium declaration behavior under a benchmark scenario and under blockchain adoption, and extend the model to settings with carrier competition and enhanced detection. Results Undeclaration motives vary with the service environment: when dangerous goods service is relatively low, service-sensitive shippers undeclare to access the faster generalcargo channel; when service is sufficiently high, price-sensitive shippers undeclare to avoid the dangerous goods tariff. The carrier’s profit-maximizing price therefore does not generally coincide with the regulatory objective of zero undeclaration. Blockchain adoption introduces two opposing forces: a service-enhancement effect that encourages truthful declaration and a cost-escalation effect that raises the dangerous goods price. As a result, blockchain reduces undeclaration only when documentation-time savings dominate the price premium induced by adoption costs; when this condition fails, adoption may increase undeclaration and reduce compliant shipper surplus. Discussion Blockchain-enabled documentation is not a universal safety remedy. Its effect on undeclaration depends on the interaction between documentation-time savings and the adoption-driven price increase, and the extensions with carrier competition and enhanced detection show that blockchain deployment should be evaluated jointly with pricing, detection, competition, and regulatory policies.

Mixed solid-state fermentation and microbial consortium improved the nutritional value of mulberry leaves and distillers’ grains - Xiaopeng Zhang; Longxiao Qin; Sha Chen; Yue Qiu; Kai Zhao; Liquan Du; Fei Xie; Yu Zeng; Jingbo Liu (World Journal of Microbiology and Biotechnology, 2026)

Maize/peanut intercropping alleviates continuous peanut cropping stress via root exudate– and rhizosphere bacteria–mediated mechanisms - Zizheng Li; Li Cui; Jie Zhang; Tingting Yi; Hong Yu; Jialei Zhang; Sha Yang; Nianyuan Jiao; Feng Guo; Shubo Wan (Soil and Tillage Research, 2026)

Interfacial carbon-regulated charge transfer and ROS evolution in Ag3PO4 for enhanced photo-persulfate activation - Jiaxin Li; Chunmu Yu; Yu Zhou; Xiaojuan Chen; Yi Hu; Yuyu Chen; Nianmin Bo; Xinyu Ke; Jiahao Cui; Sha Xiao; Chunhui Cui; Ziyue Yang; et al. (Environmental Research, 2026)

Inflammatory response involved in cartilage degeneration induced by T-2 toxin: systematic review - Qian Li; Yikai Hu; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Miao Wang; Huanxia Zhang; Yanjie Dou; Shuiyuan Yu; Fang-fang Yu (Mycotoxin Research, 2026)

A previously undescribed 3,4-secodammarane derivative from Ailanthus altissima - Yu-Sha Shi; Li-Lian Zhao; Li Huang; Su Hu; De-Feng Peng; Zhuo-Hong Li; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

Design, synthesis, and anti-prostate cancer activity evaluation of novel thieno[2,3-b]pyridine derivatives as potential BLM helicase inhibitors - Wei Tu; Ningning Zan; Xinyu Liu; Gang Yu; Xiaoping Zeng; Yafang Zhou; Jia Yu; Xueling Meng; Kun Liu; Xiaolin Peng; Sha Cheng; Bixue Xu; et al. (Molecular Diversity, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Hyperspectral response and quantitative monitoring of soil organic carbon on the Loess Plateau - Sha Yang; Zhigang Wang; Chenzhi Zheng; Yuchao Yang; Jiancheng Zhang; Xingxing Qiao; William Rickard; Yu Zhao; Meichen Feng; Longmei Gao; Wude Yang; Chao Wang (Computers and Electronics in Agriculture, 2026)

Lightweight aggregates sintered from Yellow River dredged sediment and sewage sludge: Mineral phase transformation and pore formation mechanism - Zhuo Chen; Sha Liang; Zhiming Zhang; Lianzheng Gui; Chenyang Huang; Huabo Duan; Wenbo Yu; Jiakuan Yang (Process Safety and Environmental Protection, 2026)

Functional antagonism and underlying regulatory pathways of haptoglobin splicing isoforms in the immune response of half-smooth tongue sole (Cynoglossus semilaevis) - Suxu Tan; Yixiao Hu; Wenwen Wang; Sen Han; Yu Bai; Yishuai Li; Kunpeng Shi; Shaoqing Zang; Yiming Hu; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Granular hydrogel gradient microenvironments drive functional osteochondral interface regeneration - Jing Wang; Wenbo Zhong; Chengxiang Sha; Yu Shen; Zhaowei Yin; Lingfeng Yuan; Bin Liang; Xi Zeng; Jing Zhang; Ziyi Yu (Chemical Engineering Journal, 2026)

Temperature-adaptive flexible pressure sensor based on thiol-ene click chemistry and 3D printing for wearable devices - Feiyue Zhou; Lixuan Yang; Shuqi Zhang; Yuxuan Ma; Yingtao Li; Sha Long; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Construction of a scaffold-mediated dual-enzyme display system in Komagataella phaffii with immobilized cells for continuous biocatalysis - Chaowei Zhou; Fanyu Chen; Jing Leng; Caice Liang; Yu Sha; Wenjun Sun; Huanqing Niu; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Effects of pharmacological treatment and lifestyle modification on prediabetes: a systematic review and meta-analysis of randomized controlled trials (RCTS) - Sicheng Lu; RongGuang Ge; Xinke Yu; Yiran Sha; Yihua Xu; Jie Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Simultaneous colorimetric and homogeneous electrochemical detection of furfuryl alcohol based on peroxidase-like activity of MXene/Mn-MOF composite - Meng Wang; Shaojun Wu; Jun Zhan; Shao-Hua Wen; Huining Xu; Sha Yu; Yuanzhen Zhou (Analytica Chimica Acta, 2026)

A Splice-Site Variant in ACY1 Associated with Congenital Hearing Loss: Clinical, Biochemical, and Zebrafish Functional Evidence - Sha Yu; Zhenmin Xu; Huijun Wang; Liheng Chen; Shao Wei Hu; Yunfei Zhang; Huiying Lyu; Hongjiang Wu; Mengyuan Wu; Yilai Shu; Wenxia Chen (Biochemical Genetics, 2026)

Host filtering shapes diversity and community stability of Symbiodiniaceae in Tridacna maxima across the Nansha Archipelago in the South China Sea - Siqi Yu; Min Hui; Haojun Chi; Xinhui Yang; Zheng Zhang; Zhongli Sha (Frontiers in Marine Science, 2026)
The giant clam-Symbiodiniaceae symbiosis represents a classic mutualism in coral reef ecosystems, driving photosynthesis and nutrient cycling that fuel reef productivity. However, it remains unclear how association with a host influences the composition and stability of Symbiodiniaceae communities, and the extent to which these communities reflect or diverge from the surrounding free-living pool. Addressing this question, high throughput Symbiodiniaceae ribosome DNA Internal Transcribed Spacer 2 (ITS2) metabarcoding sequencing was performed in 48 seawater and Tridacna maxima mantle samples collected across three atolls of the Nansha Archipelago in the South China Sea. Compared with the highly diverse free-living pool in the surrounding water (680 amplicon sequence variants, ASVs; 11 ITS2 types), symbiotic communities exhibited significantly lower number of Symbiodiniaceae ITS2 types (247 ASVs; five ITS2 types). Free-living communities differed markedly among reefs primarily driven by geographical distance, and concentrations of various nutrients and heavy metals, whereas clam-associated communities remained spatially homogeneous. Symbionts were dominated by Cladocopium C1 and Symbiodinium A3, reflecting the host’s selection of Symbiodiniaceae. Moreover, clam-associated communities were predominantly shaped by deterministic processes and exhibited higher community stability, whereas free-living communities were co-influenced by deterministic and stochastic processes. This low species diversity yet high stability of symbiotic communities implies functional diversity among dominant genera might play a key role in maintaining holobiont resilience, whose stability could be reinforced by the buffered microenvironment created by the giant clam. These findings highlight the importance of host-mediated structuring of Symbiodiniaceae communities for holobiont stability and suggest that maintaining host-symbiont integrity maybe important for reef ecosystem resilience under environmental change.

Microwave pretreatment assisted regulation of surface oxygen density and narrow micropores of bamboo-based porous carbon for effective CO2 capture and H2 adsorption - Wanying Wang; Lishu Shao; Yongzhen Li; Xiancheng Ma; Weigang Zhao; Lei Li; Sha Luo; Yu Liao; Yan Qing (Journal of Environmental Chemical Engineering, 2026)

White peroxidase-mimicking Mn-MOF enabled smartphone-assisted colorimetric sensor for on-site visual detection of perfluorooctane sulfonate in water samples - Shao-Hua Wen; Jun Zhan; Hao Wu; Yule Ji; Qingpeng Zhao; Ziqi Yuan; Junping Ma; Sha Yu; Yuanzhen Zhou; Man Ge (Journal of Environmental Chemical Engineering, 2026)

A full active pharmaceutical ingredients-based nanoplatform potentiates tumor immunotherapy via multidimensional cGAS-STING pathway activation - Jun Wang; Jun Yin; Tao Kuang; Zhi Zheng; Yin Liu; Xiaofei Liu; Sha Liu; Suisui He; Cui-Yun Yu; Hua Wei (Chemical Engineering Journal, 2026)

Conformation-controlled chain packing in bio-based networks for efficient photothermal conversion - Yu Bei; Ye Sha; Yun Hu; Meng Zhang; Tianyu Zhu; Yonghong Zhou; Puyou Jia (Chemical Engineering Journal, 2026)

Genome-Wide Analysis and Characterization of CYP450 Gene Family in Tobacco (Nicotiana tabacum L) - Yunfei Sha; Senwen Yu; Zhenbo Cai; Zhe Zhang; Kangkang Song; Long Yang; Xia Shao (Plant Molecular Biology Reporter, 2026)

Response of offshore wind turbine monopile-liquefiable seabed-seawater coupled system to vertical and horizontal seismic excitations - Chen Wang; Jia-Jia Xu; Ye-Jun Sun; Jun Wang; Fei Cai; Dong Cai; Zheng-Hai Sha; Feng-Xue Jin; Ling-Yu Xu (Frontiers in Marine Science, 2026)
A comprehensive understanding of the underlying mechanisms governing offshore wind turbine (OWT) response in liquefiable seabeds during seismic events remains incomplete, particularly with respect to vertical ground motion components and tripartite seawater-structure-soil interaction dynamics. A 3D integrated monopile-seabed-seawater model for a monitored 6.45-MW OWT is developed, featuring acoustic elements for seawater hydrodynamics, advanced constitutive models for liquefaction and material damping, and coupled vertical-horizontal seismic input. The dynamic characteristic of the OWT is rigorously validated through ​continuous vibration acceleration monitoring. Key findings reveal that: (1) Increasing monopile embedment depth in non-liquefied soil layers effectively mitigates liquefaction-induced residual lateral displacements; (2) Monopile vertical displacement amplitude depends critically on both seismic input frequency and the phase difference between horizontal/vertical peak ground accelerations; (3) Seawater presence restrains monopile displacements, while neglecting seabed-seawater coupling leads to underestimated excess pore water pressure (EPWP) buildup in shallow seabed layers during seismic events; (4) Vertical seismic motion dominates seawater’s influence on OWT seismic response by coupling with hydrodynamic pressure to amplify the EPWP changes in liquefiable seabeds. The results demonstrate that comprehensive consideration of coupled vertical seismic excitation and fluid-soil-structure interaction is essential for accurate liquefaction assessment of OWT foundations.

Peroxisome proliferator-activated receptor γ coordinates the “growth-defense trade-off” in intensive aquaculture of grass carp (Ctenopharyngodon idella) - Wenting Huang; Shaoqing Zang; Hui Liu; Xinlu Ren; Ruixue Zhang; Yu Yang; Wenwen Wang; Suxu Tan; Tingting Li; Kunpeng Shi; Zhenxia Sha (Aquaculture, 2026)

Plastisphere denitrification dynamics shaped by soil acidification: Microbial Community and activity responses - Yu-Chen Li; Sha Zhao; Hu Li; Pei-Yuan Xu; Hong-Xia Cui; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Phage-based suppression of plasmid-mediated antibiotic resistance: A promising approach for antimicrobial stewardship - Yan-Zi Wang; Hu Li; Bei-Ning Xue; Xiao-Xu Zhao; Yu Rao; Sha Zhao; Kiandro J. Fortuna; Mao Ye; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

Interfacial biomimetic engineering synergizing with mycelium: Constructing high-strength, water-resistant, and flame-retardant formaldehyde-free composites - Junqiang Shan; Yajuan Cao; Yanjun Chen; Yingye Shen; Tianpeng Chen; Yu Sha; Wenjun Sun; Yong Chen; Hanjie Ying (Chemical Engineering Journal, 2026)

miR-133a-3p promotes T-2 toxin-induced chondrocyte damage via targeting IGF1R - Kangting Luo; Lingyu Wang; Zhengyan Zhang; Yikai Hu; Chengyu Zhao; Shuiyuan Yu; Qian Li; Zaichao Dong; Tongtong Sha; Miao Wang; Juan Zuo; Yanjie Dou; et al. (Chemico-Biological Interactions, 2026)

Engineering Escherichia coli cell Factories for continuous 5′-cytidine monophosphate production via biofilm-anchored dual-enzyme cascade catalysis - Wenjun Sun; Shiya Zhu; Qiwei Dong; Shuyan Tang; Qingguo Liu; Yu Sha; Tianpeng Chen; Rui Wang; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Targeted external donor dosing in single-stage partial nitritation-anammox: A carbon-efficient control framework sustaining ultrahigh total nitrogen removal - Chengcheng Lin; Yanxiao Wei; Sha Wu; Jiao Jin; Yangkai Liu; Hong Chen; Hanbo Yu; Mohd Fadhil Md Din; Eli Hendrik Sanjaya; Binquan Wang (Process Safety and Environmental Protection, 2026)

Improving the dewaterability of municipal wastewater sludge and EPS oxidation by PbO2 anodic electrocatalytic process: Effective factors and process optimization - Luxiang Cai; Zhentian Cai; Desong Zhu; Haolei Sha; Guoying Yu (Journal of Environmental Management, 2026)

Identification of microplastics in landfill leachate: An underestimated tiny microplastics using Focal Plane Array (FPA)-based Fourier Transform Infrared (FTIR) imaging - Shijie Bian; Timing Jiang; Jingwei Yan; Rui Cai; Shushan Yuan; Wenbo Yu; Sha Liang; Liang Huang; Huabo Duan; Mukesh Kumar Awasthi; Jiakuan Yang (Journal of Environmental Sciences, 2026)

Magnetic controlled label-free homogeneous electrochemical biosensing of aflatoxin B1 based on Nanochannel-gated signal amplification strategy - Jingyu Zhang; Junping Ma; Bijun Zhao; Zezhou Kang; Xiaoli Liu; Yizhe Wang; Yuanzhen Zhou; Sha Yu; Shaohua Wen; Jianbin Zheng; Wushuang Bai (Food Chemistry, 2026)

Enzymatic hydrolysis affected the antioxidant activity and traceability identification of porcine collagen peptides - Yu-Ting Hu; Zong-Cai Tu; Guang-Xian Liu; Chun-Yan Peng; Peng Zhang; Wen-Ming Xie; Le-Ying Yang; Yu Chen; Zi-Zi Hu; Xiao-Mei Sha (Food Chemistry, 2026)

Construction of interpenetrating polymer network (IPN) based on insoluble soybean fiber cross-linked fish gelatin and its synergistic mechanism in coating preservation of sturgeon - Tian Yang; Mingzheng Huang; Lei He; Yingmei Wu; Yan Zhou; Xiaomei Sha; Qun Huang; Meijuan Yu; Xin Li (Food Hydrocolloids, 2026)

Histone H3K27 acetylation of slc25a4 mediates triclocarban-induced transgenerational developmental toxicity in zebrafish (Danio rerio) at subthreshold exposure - Yiming Chang; Zijian Su; Xinyi Jiang; Sihan Huang; Jialing Yu; Zhanyou Li; Keke Liu; Zhijian Sha; Lu Yang; Xiaojia Chen; An hong; Yibo Zhang; et al. (Environmental Research, 2026)

Generation and Exosomal Noncoding RNA Profiling of Down Syndrome-Specific Induced Pluripotent Stem Cells - Chunxia Li; Weiwei Gong; Gengshuo Chen; Yu Sha; Chune Mo; Jiajun Xu; Xianliang Hou; Minglin Ou (Stem Cell Reviews and Reports, 2026)

Genome-wide CRISPR/Cas9 knockout screen identifies host factors essential for bovine parainfluenza virus type 3 replication - Jinyang Hao; Xiaoran Gao; Christine Light; Yuze Sun; Sha Lu; Yu Tian; Xia Gao; Yuan Su; Jie Gao; Xin Huang; Qianyi Zhang; Jinliang Wang; et al. (Science China Life Sciences, 2026)

RPB2 gene phylogeny of species in Penthorum L. and related genera - Yan Wang; Sha Yi; Bin Wang; Weiya Wang; Haiqing Yu; Xin Shu (Biologia, 2026)

Advanced strategies for selective lithium extraction from spent lithium-ion battery cathodes - Ying Zheng; Ziwen Dai; Fan Yang; Zhaoyang Li; Guang Hu; Sha Liang; Wenbo Yu; Shushan Yuan; Huabo Duan; Liang Huang; Jingping Hu; Huijie Hou; et al. (Resources, Conservation and Recycling, 2026)

Maternal mRNA clearance is associated with the prevention of precocious transcription and genome instability in mouse early embryos - Qian-Qian Sha; Yun-Wen Wu; Meng-Yan Jia; Yu Jiang; Xing-Xing Dai; Long-Wen Zhao; Heng-Yu Fan (Science Bulletin, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Flavor profiles and microbial mechanisms of suansun: A comparative study of homemade and commercial production - Qiao Qian; Zheng-Pei Chen; Ke Li; Sha-Sha Fang; Zhen-Ming Lu; Hong-Yu Xu; Zheng-Hong Xu (International Journal of Food Microbiology, 2026)

Genomic selection accelerates genetic improvement of tolerance to visceral nodular disease in the half-smooth tongue sole (Cynoglossus semilaevis) - Mengyang Chang; Kunpeng Shi; Jibin Shen; Yu Yang; Yishuai Li; Jiayu Cheng; Xiangming Cheng; Yingming Yang; Zhongkai Cui; Songlin Chen; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Genome-wide DNA methylation response of Paralichthys olivaceus to Ulva prolifera decomposition effluent stress - Yu Yang; Kunpeng Shi; Jie Ma; Mengyang Chang; Yishuai Li; Suxu Tan; Ruixue Zhang; Xinlu Ren; Xiaoyong Shi; Zhenxia Sha (Environmental Pollution, 2026)

From laboratory to industrial scale: How to evaluate the carbon mineralization of cement and cement-based materials - Sining Lyu; Qiuxia Zou; Junda Quan; Ning Zhang; Kairui Hu; Lianzheng Gui; Wenbo Yu; Sha Liang; Huabo Duan; Jiakuan Yang (Environmental Impact Assessment Review, 2026)

Intranasal biomimetic vesicle platform reprograms the glioblastoma microenvironment for enhanced immunotherapy - Shuo Li; Chao Qin; Fan-Yu Qian; Jin-Hao Wang; Xiang-Gui Wu; Wen-Qing Li; Tai-Yu Liu; Zhao-Jie Chen; Bei-Yuan Zhang; Qi-Yue Liu; Li-Sha Liu; Li-Fang Yin (Chemical Engineering Journal, 2026)

One-step rapid synthesis Ti-O-rich Ti3C2 MXene via NH4HF2 hydrothermal etching for high charge storage - Xuefeng Sha; Xianyin Song; Qiwei Shangguan; Yawei Lv; Fan Zeng; Xingang Zhang; Xueli Wu; Minghao Yu; Changzhong Jiang (Chemical Engineering Journal, 2026)

Engineering Escherichia coli for continuous L-valine production via two-stage biofilm and metabolic regulation - Wenjun Sun; Yu Sha; Shuqi Shi; Wenlu Qi; Qingguo Liu; Tianpeng Chen; Yong Chen; Hanjie Ying (Chemical Engineering Journal, 2026)

Engineering living bio-hybrid materials for sustainable l-threonine production - Shuqi Shi; Jinming Zhang; Shiya Zhu; Yu Sha; Qingguo Liu; Tianpeng Chen; Wenjun Sun; Wei Zhuang; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Dynamic audio–visual fusion for accurate fish feeding intensity recognition in recirculating aquaculture environments - Yida Sha; Junfeng Wu; Saibei Zheng; Peihua Wu; Shaojiang Cheng; Miao Chen; Yizhi Zhou; Hong Yu (Aquaculture International, 2026)

Study on the dynamic interaction between buried bent pipes and soil under the influence of oblique incidence of SV waves - Chang-lu Xu; De-long Huang; Hui-yue Wang; Sha-sha Yu; Huan-qing Song; Hang Cen; Zi-yuan Huang; Qiang Liu; Ai-ping Tang (Soil Dynamics and Earthquake Engineering, 2026)

Numerical investigation on the influence of temperature on combustion and emission characteristics of NH3/H2/CH4 mixtures under gas turbine conditions - Yanfei Zhang; Qing Hao; Mingming Huang; Zhenxian Liu; Qin Li; Zewen Yu; Jianfang Du; Xiao Zhang; Zhuoming Xiong; Qingkui Zhang; Yumeng Cao; Haoxi Sha (Fuel, 2026)

Glucosamine-triggered sustainable redox process for efficient degradation of tetracycline antibiotics - Tengli Zhang; Peng Jin; Mengting Liu; Jiao Sha; Xunqin Gao; Luqiu Feng; Hong Yao; Xiwang Liu; Hao Shao; Yinglan Yu; Zhiguo Fang; Lei Luo (Chemical Engineering Journal, 2026)

Identification of TMED10 as A Regulator for Neuronal Exocytosis of Amyloid Beta 42 - Peixin Meng; Longze Sha; Xiaolin Yu; Yanbing Wang; Erning Zhang; Kexin Meng; Bingnan Li; Qin Zhao; Qi Xu (Neuroscience Bulletin, 2026)

Systematic druggable genome-wide Mendelian randomization identifies therapeutic targets for gout - Wei-quan Liao; Hui-ying Chen; Yu-ying Li; Li-juan Xiao; Zai-xing Qiu; Sha-sha Hu; Si-hui He; Lan Luo; Jing-jing Xie; Jian-yong Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

GHG emission and reduction of crop residue biochar-based products in different soils: insights from prospective life cycle assessment - Yinan Liu; Yaxi Fang; Hanbing Li; Sumei Li; Sha Chen; Yu Li; Peize Wu (ENGINEERING Environment, 2026)

Quality Assessment of Cloud Detection and Cloud Top Height Products from FY-3D/MERSI-II in Polar Regions - Caixia Yu; Xiuqing Hu; Dong Liu; Yanyu Lu; Jin Sha (Journal of Meteorological Research, 2026)

Response of soil nematode community to alpine meadow degradation and restoration in the Three Rivers source region - Yuanze Li; Fei Yu; Xueying Huo; Yang Wu; Wenjing Chen; Sha Xue (Applied Soil Ecology, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Lanthanum-quaternized chitosan-modified zeolite for long-lasting operation of constructed wetland: A bifunctional strategy for simultaneous phosphorus removal and microbial clogging mitigation - Ling Wang; Jian-Guo Zhang; Hong-Yin Sha; Yi-Ru Wang; Hao-Yu Wang; Guang-Can Zhu; Yong-Ze Lu (Water Research, 2026)

Enhanced full-process method for the quantitative analysis of PFAS in sludge: Robust extraction and matrix effect-minimized method - Song Li; Jingwei Yan; Wanying Zhai; Wenbo Yu; Timing Jiang; Jing Chen; Xiaofeng Bai; Sha Liang; Shushan Yuan; Huabo Duan; Jiakuan Yang (Water Research, 2026)

Phylogenomic framework, biogeography and character evolution of the genus Campylotropis (Fabaceae, Papilionoideae) - Li-Sha Jiang; Yu Feng; Jun-Yi Zhang; Xiong Li; Min Liao; Heng-Ning Deng; Qi Yu; Bo Xu (Molecular Phylogenetics and Evolution, 2026)

China's household water demand scenarios under the carbon neutrality transition - Yu-Jie Jiao; Ke-Jun Jiang; Chen-Min He; Sha Chen; Pian-Pian Xiang (Journal of Cleaner Production, 2026)

Tissue-specific metabolite profiling of alkaloids and flavonoids in lotus cultivated in China enables rational resource utilization - YueTong Yu; Jing Que; Hedi Zhao; Gangqiang Dong; Yingli Wang; Ling Yuan; Sha Chen (Food Chemistry, 2026)

Integrating machine learning with lateral flow immunoassay for ultrafast and sensitive tadalafil detection - Jiawei Chen; Zhenzhen Chen; Sha Yu; Xiaoyue Xiao; Juan Peng; Yudi Xia; Weihua Lai (Food Chemistry, 2026)

Covalent organic framework/PVA membranes for efficient phosphoric acid concentration via pervaporation - Wuqi Cai; Dongpu Hu; Huying Li; He Wen; Yimeng Shi; Jing Wang; Ziwen Dai; Wenbo Yu; Sha Liang; Jiakuan Yang; Shushan Yuan (Desalination, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Dynamic hydrolytic ion-pairing enables stable interfaces and high anode utilization in lean-electrolyte Mg-air batteries - Yuxi Zhang; Sensen Yu; Ming Li; Sha Luo; Yu Feng; An Duan; Bao Zhang; Wei Sun (Chemical Engineering Journal, 2026)

HIF-1α/BNIP3L–mediated mitophagy is involved in T-2 toxin–induced myocardial injury - Qian Li; Miao Wang; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Huanxia Zhang; Yanjie Dou; Guoyu Zhou; Yue Ba; Fang-fang Yu (Chemico-Biological Interactions, 2026)

Analysis of odor and VOCs pollution in industrial parks of central inner Mongolia autonomous region based on mobile monitoring - Chaofei Li; Yuanhao Jia; Yu Qiu; Cheryl Marie Cordeiro; Sha Li; Yanying Chen; Jinxing Liu; Heinz W. Siesler; Hongkan Wu; Run Zhao (Atmospheric Environment, 2026)

Spatiotemporal evolution of the cooling effect of blue-green space in different LCZs: A comparative study of Wuhan and Shanghai (2000−2022) - Yazhou Qi; Chunxiao Zhang; Sha Pei; Hanguang Yu; Yuqian Hu (Urban Climate, 2025)

Ca(II) alleviates microplastic toxicity to Microcystis aeruginosa via cyanobacteria induced carbonate precipitation - He-Wei Song; Jing An; Jia-Qi Sha; Fang-Yu Hu; Wei-Tao Liu (Journal of Hazardous Materials, 2025)

Tannic acid-triggered functional coatings for the regulation of surface charge, cell adhesion and semi-continuous fermentation - Yu Sha; Yong Gao; Jinming Zhang; Tianpeng Chen; Qingguo Liu; Chenjie Zhu; Pengpeng Yang; Hanjie Ying; Yong Chen; Wenjun Sun; Wei Zhuang (Journal of Environmental Chemical Engineering, 2025)

Boosting photoactivation of microorganisms by covalent binding of nanoparticles to membrane proteins - Zi-Jie Lu; Chong Sha; Tian-Yu Zhu; Jun-Ying Liu; Yang-Chun Yong (Chemical Engineering Journal, 2025)

CDK5-Induced HCN2 Channel Dysfunction in the Prelimbic Cortex Drives Allodynia and Anxiety-Like Behaviors in Neuropathic Pain - Lu Chen; Shuai Cao; Yun-Ze Liu; Qi-Fan Yang; Jin-Yu Yang; Dan-Yang Zhang; Guo-Guang Xie; Xiang-Sha Yin; Ying Zhang; Yun Wang (Neuroscience Bulletin, 2025)

Prevalence and spectrum of STRC variants in 1015 sensorineural hearing loss patients: insights from the Chinese population - Luo Guo; Sha Yu; Wenrui Zhao; Liheng Chen; Guiqing Cheng; Weitao Li; Wei Li; Haiting Ji; Shan Sun; Huiqian Yu; Haiying Liu; Chunyi Gui; et al. (Molecular Genetics and Genomics, 2025)

Genetic analysis of patients with low-frequency non-syndromic hearing loss - Sha Yu; Weitao Li; Xinhao Lin; Liheng Chen; Wenxia Chen; Luo Guo; Yilai Shu (Molecular Genetics and Genomics, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Blocking triggering receptors expressed on myeloid cell-1 alleviates alveolar epithelial cell senescence by inhibiting oxidative stress in pulmonary fibrosis - Wen-Jing Zhong; Jian-Bing Xiong; Chen-Yu Zhang; Ling Jin; Nan-Shi-Yu Yang; Han-Xi Sha; Yu-Biao Liu; Jia-Xi Duan; Cha-Xiang Guan; Yong Zhou; Feng Su (Histochemistry and Cell Biology, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

Di(2-ethylhexyl) phthalate reduces the ginsenoside content in Panax ginseng root exudates by disrupting rhizosphere microbe-mediated soil nitrogen cycling - Lu Yu-Shun; Li Shan-Shan; Sha Ji-Yue; Chen Jian-Bo; Huo Xiao-Hui; Xu Yan-Yang (Applied Soil Ecology, 2025)

LncRNA SNHG16 Drives PD-L1-Mediated Immune Escape in Colorectal Cancer through Regulating miR-324-3p/ELK4 Signaling - Zhiyuan Chen; Zhenjuan Wu; Minghao Wu; Yu Zhang; Sha Hou; Xiangyang Wang; Ya Peng (Biochemical Genetics, 2025)

OWTDNet: A Novel CNN-Mamba Fusion Network for Offshore Wind Turbine Detection in High-Resolution Remote Sensing Images - Pengcheng Sha; Sujie Lu; Zongjie Xu; Jianhai Yu; Lei Li; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2025)
Real-time monitoring of offshore wind turbines (OWTs) through satellite remote sensing imagery is considered an essential process for large-scale infrastructure surveillance in ocean engineering. Current detection systems, however, are constrained by persistent technical limitations, including prohibitive deployment costs, insufficient discriminative power for learned features, and susceptibility to environmental interference. To address these challenges, a dual-branch architecture named OWTDNet is proposed, which integrates global contextual modeling via State Space Models (SSMs) with CNN-based local feature extraction for high-resolution OWTs detection. The primary branch utilizes a Mamba-structured encoder with linear computational complexity to establish long-range spatial dependencies, while an auxiliary Blurring-MobileNetv3 (B-Mv3) branch is designed to compensate for the local feature extraction deficiencies inherent in SSMs. Additionally, a novel Feature Alignment Module (FAM) is introduced to systematically coordinate cross-modal feature fusion between Mamba and CNN branches through channel-wise recalibration and position-aware alignment mechanisms. This module not only enables complementary feature integration but also enhances turbine-specific responses through attention-driven feature modulation. Comprehensive experimental validation demonstrated the superiority of the proposed framework, achieving a mean average precision (AP) of 47.1% on 40,000 × 40,000-pixel satellite imagery, while maintaining practical computational efficiency (127.7 s per image processing time).

The lysosomal cysteine protease cathepsin L promotes stemness and multidrug resistance of non-small cell lung cancer by targeting HGF activator - Hui Shi; Jianyu Xu; Juan Wu; Sha Hu; Xi Chen; Qianfang Hu; Qian Liu; Yanxia Yu; Xinyuan Ding; Wenjuan Wang (Molecular and Cellular Biochemistry, 2025)

Disorder and Mg concentration effects on equilibrium C-O isotope fractionations in Mg Ca1-CO3 solid solutions (0 ≤ x ≤ 0.5): A crystallographic and spectroscopic study of magnesian calcite and dolomite - Yunfan Miao; Xi Zhu; Yu Ye; Zhengrong Wang; Qingbo Wang; Dan Liu; Sha Wang; Yancheng Hu; Zhen Wu (Geochimica et Cosmochimica Acta, 2025)

SHP-1 regulates T cell-mediated early adaptive immunity in Chinese tongue sole (Cynoglossus semilaevis) infected with Mycobacterium marinum - Muyuan Wang; Suxu Tan; Jin Liu; Mengyang Chang; Ningning Wang; Hongning Liu; Weijun Zhang; Jinqi Xia; Yu Yang; Wenting Huang; Zhenxia Sha (Fish & Shellfish Immunology, 2025)

Associations of environmental toxicant exposure with adult sleep problems and the mediating roles of inflammation - Lu-Jia Li; Wen Zhang; Daniel Yee-Tak Fong; Ji-Bin Li; Yu-Hui Kou; Sha Li; Xiao-Yong Chen; Wei-Jie Gong (Environmental Pollution, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

Unveiling dynamics of microbial communities, species interactions, and ecological assembly during low-temperature-induced sludge bulking in full-scale wastewater treatment systems - Han-Jun Sun; Xian Zhao; Jie Ding; Yu-Qian Wang; Wen-Shuo Wang; Zhi-Hua Feng; Sha Zhao; Liang Wang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2025)

Disrupted Lipid Metabolism Aggravates Ischemic Brain Injury: Targeting FDFT1 for Stroke Therapy - Jing Yuan; Yu-Sha Liao; Tie-Chun Zhang; Shuang Liu; Min-Min Ruan; Ting-Ting Yang; Shi-Qi Sun; Long-Yao Xu; Xiao-Long Xie; Ling Zhao (Molecular Neurobiology, 2025)

Overcoming body occlusion challenges: a novel underwater fish individual recognition based on local and global feature fusion - Xuelan Liang; Junfeng Wu; Yongzhi Xie; Miao Chen; Shaojiang Cheng; Yida Sha; Peihua Wu; Saibei Zheng; Hong Yu (Aquaculture International, 2025)

Ifeed: intelligent feeding decision-making for farmed fish via density distribution similarity measurement - Yongzhi Xie; Junfeng Wu; Xuelan Liang; Shaojiang Cheng; Yida Sha; Hong Yu (Aquaculture International, 2025)

Woody Plant Encroachment Significantly Alters Grassland Soil Microbial Community: A Global Meta‐Analysis - Guoliang Sha; Shuyan Chen; Xuanchen Liu; Wanyu Xia; Hanwen Cui; Anning Zhang; Lizhe An; Zi Yang; Xia Zhao; Jing Zhang; Xiuling Yu; Jing Xiao; et al. (Global Ecology and Biogeography, 2025)
Aim Woody plant encroachment is reshaping grassland ecosystem functions worldwide. While its aboveground impacts are well documented, how this process alters microbial communities—key drivers of belowground processes—remains poorly understood. We aimed to (1) quantify the general effects of global woody plant encroachment on soil microbial community attributes in grasslands and (2) identify the abiotic and biotic factors driving these changes. Location Global grassland ecosystems. Time Period 2000–2024. Major Taxa Studied Soil microbial communities (bacteria, fungi). Methods We conducted a meta‐analysis of 241 paired observations to evaluate changes in microbial composition, diversity, biomass, activity and enzyme activity under woody plant encroachment. Results Woody plant encroachment significantly altered soil properties. Woody plant encroachment also promoted a comprehensive increase in microbial community diversity, biomass, microbial activity and enzyme activity, as well as changes in community composition. The nitrogen‐fixing status of the encroaching species (biotic factor) significantly affected microbial responses: encroachment by nitrogen‐fixing plants resulted in a higher abundance of Bacteroidetes, fungal richness, microbial biomass phosphorus and phosphatase activity compared to non‐nitrogen‐fixing plants. In addition, abiotic factors, such as mean annual temperature, soil organic carbon and total nitrogen were identified as key factors driving microbial responses. Specifically, mean annual precipitation, mean annual temperature and elevation jointly regulated the effects of woody plant encroachment on soil microbial community attributes by influencing plant and soil properties. Main Conclusions This meta‐analysis demonstrated that woody plant encroachment significantly reshaped soil microbial communities in grassland ecosystems. Our findings highlight the role of abiotic factors (climate, elevation, organic carbon and total nitrogen), and biotic factors (nitrogen‐fixing status) in mediating the response of soil microbial communities. These insights contribute to a better understanding of belowground ecological processes and provide valuable guidance for grassland management and predictions of biogeochemical cycles under global change.

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

A critical review of oxygen supply and control strategies in single-stage partial nitritation-anammox system for autotrophic nitrogen removal from wastewater - Sha Wu; Fei Gao; Chengcheng Lin; Yijie Quan; Yanxiao Wei; Zhihua Liu; Hanbo Yu; Eli Hendrik Sanjaya; Mohd Fadhil Md Din; Hong Chen (Journal of Environmental Chemical Engineering, 2025)

Changes in physical properties and characteristic peptides in porcine gelatin-containing gummy candies at different storage stages during shelf-life - Le-Ying Yang; Zong-Cai Tu; Hui Wang; Xue-Ke Sun; Yu-Ting Hu; Yu Chen; Zi-Zi Hu; Xiao-Mei Sha (Food Hydrocolloids, 2025)

Hemostatic Janus sponge for coagulopathic wounds: Robust wet adhesion and procoagulant activity accelerates hemostasis and healing - Yajun Zhang; Meng Yang; Yanqiu Leng; Huaibin Gong; Sha Jiang; Bitao Lu; Kun Yu; Guangqian Lan (Chemical Engineering Journal, 2025)

Synergistic integration of light signal, hormone dynamics, and carbohydrate metabolism orchestrates rhizome bud development in Arundo donax - Xinyu Tan; Long Sha; Baoming Tian; Mingchen Yu; Zhengqing Xie; Weiwei Chen; Yixin Huangfu; Jialin Guo; Jiayin Liu; Chao Deng; Fang Wei; Gongyao Shi (Planta, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

Mechanisms of groundwater recovery and land subsidence mitigation in a piedmont plain - Long Zhao; Xiao-Wei Jiang; Yu-Mei Li; Yong Luo; Kun-Chao Lei; Wen-Jie Kou; Fang Tian; Miao-Zhuang Tian; Te Sha; Shu-Fang Wang; Wen-Jun Cui (Journal of Hydrology, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Coupling covalent organic framework with polyacrylamide to construct a robust composite hydrogel electrolyte for dendrite-free and long-lifespan aqueous zinc-ion batteries - Ziming Liu; Xiangcai Li; Heng Zhang; Xuke Zhang; Junyuan Li; Yifei Shi; Dongxiang Geng; Zhaolei Li; Dawei Sha; Genxi Yu; Chao Yan (Chemical Engineering Journal, 2025)

Charge/conformation-transformable phosphopeptide@hollow covalent organic frameworks as molecular gates for electrochemical analysis - Lin Wang; Minghui Wang; Gaoxiang Wang; Haojie Xie; Yu Hang; Dongmei Zhang; Sha Zhu; Xiafei Hu; Genxi Li (Chemical Engineering Journal, 2025)

Tamoxifen regulates ferroptosis of hepatocytes by targeting SLC1A5 to activate hepatic stellate cells and liver fibrosis - Sha Shi; Meiling Zhang; Chengkai Zhu; Shanhao Zhu; Jie Yu; Qi Sui; Jiaqi Xu; Juan Ren; Jingnan Zhang; Peng Chen; Yi Zhang (Chemico-Biological Interactions, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

Oak pollen infrageneric classification-based winter temperature reconstruction since the marine isotope stage 5 in Southeast China - Yinning Tang; Lu Dai; Fei Gong; Junjie Yu; Jilong Wang; Weijian Zeng; Limi Mao; Zhongjing Cheng; Longbin Sha (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Hydroxyl-tunable type I photosensitizer based on curcumin for photodynamic therapy against hypoxic tumor cells - Yanping Wang; Tong Mu; Xuewei Li; Xiuli Zheng; Jie Sha; Zhe Yu; Yuanyuan Qin; Haohui Ren; Ying Wang; Weimin Liu; Pengfei Wang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Soil C-N and microbial community were altered by polybutylene adipate terephthalate microplastics - Yao Yu; Yan Wang; Darrell W.S. Tang; Sha Xue; Mengjuan Liu; Violette Geissen; Xiaomei Yang (Journal of Hazardous Materials, 2025)

Closed-loop recyclable bio-based covalent adaptable networks for high-efficiency UV shielding - Ting Luo; Ye Sha; Yu Bei; Zhonglei Meng; Yun Hu; Meng Zhang; Yonghong Zhou; Puyou Jia (Chemical Engineering Journal, 2025)

Comparison of indoor thermal comfort of the elderly in urban, suburban rural and mountainous rural areas in South China karst - Xinzhi Gong; Sha Lai; Qinglin Meng; Mattheos Santamouris; Yilei Yu; Lei Zhang (Building and Environment, 2025)

Electroacupuncture may alleviate inflammatory pain by downregulating the expression of P2Y14 receptor in the primary somatosensory cortex - Shuai Hou; Cui-Yuan Chen; Rui-Zhu Zhou; Liu-Xuan He; Xiao-Xiao Zhao; Sha-Sha Chen; Sha Yang; Hai-Yan Yin; Shu-Guang Yu (Purinergic Signalling, 2025)

Exploring mechanisms of radiation-induced myocardial fibrosis using HMGB1 neutralizing antibody - Gang Wang; Bi-Bo Wu; Sha-Sha Zhao; Jing Zhang; Yu Wang; Yin-Xiang Hu; Jun Wan; Bing Lu; Sheng-Fa Su (Journal of Molecular Histology, 2025)

Landfill depths alter microbial community structure and ecological assembly by affecting δ13C and organic matter - Yu-Xin Wang; Qing-Yu Liu; Jun-Yan Du; Hao-Qun Sha; Jing Su; Yue Sun; Jing-Ying Mao; Xiao-Song He (Waste Management, 2025)

Fabrication and verification of novel 3D FBG-based transducer for directly measuring vertical and lateral effective stresses - Tian-Yu Zhang; Sha Lai; Wei-Qiang Feng (Ocean Engineering, 2025)

Dual-strategy enhanced lateral flow immunoassay based on matrix tolerant antibody and bright aggregation-induced emission label for the sensitive detection of sildenafil - Jiawei Chen; Xinhui Shu; Xiaoyue Xiao; Gan Zhang; Sha Yu; Juan Peng; Weihua Lai (Food Bioscience, 2025)

Enhanced hydrogen production by robust covalent biohybrid based on cell membrane specific click chemistry - Tian-Yu Zhu; Yi-Cheng Zhao; Chong Sha; Said Nawab; Jun-Ying Liu; Yang-Chun Yong (Bioresource Technology, 2025)

Ultrasensitive electrochemical sensor based on Cr-doped Co3O4@NiO hybrid for precise simultaneous detection of trace multiple heavy metal ions - Junping Ma; Yu Wei; Sha Yu; Jieli Tang; Shaohua Wen; Shuangli Chen; Yuanzhen Zhou (Journal of Environmental Chemical Engineering, 2025)

Integrating Bulk RNA and Single-Cell Sequencing Data Unveils Efferocytosis Patterns and ceRNA Network in Ischemic Stroke - Jing Yuan; Yu-sha Liao; Tie-chun Zhang; Yu-qi Tang; Pei Yu; Ya-ning Liu; Ding-jun Cai; Shu-guang Yu; Ling Zhao (Translational Stroke Research, 2025)

Degradable microplastics induce more soil organic carbon loss via priming effects: a viewpoint - Zhenyu Yang; Ying Sha; Amit Kumar; Zhiguo Yu; Junjie Lin; Yan Lei (Plant and Soil, 2025)

Correction: Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Hotspots and future trends of biomarker research in oral squamous cell carcinoma: a comprehensive bibliometric analysis - Jingqi Liu; Yu Cai; Kaifang Wang; Beiyuan Chen; Nan Liu; Ou Sha (Genome Instability & Disease, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Detection of arsenate in colored grains using an interference-free dual-signal ratiometric HEC sensor - Shao-Hua Wen; Ning Wang; Ziqi Yuan; Hao Wu; Gege Yan; Hengyuan Zhang; Sha Yu; Junping Ma; Yuanzhen Zhou (Food Chemistry, 2025)

Multiple stimuli-responsive circularly polarized luminescent bio-composite films by coassembling cellulose nanocrystals and curcumin - Shaoyi Cao; Jingpeng Wang; Wenye Sun; Bang An; Mingcong Xu; Sha Luo; Chunhui Ma; Haipeng Yu; Zhijun Chen; Jian Li; Wei Li; Shouxin Liu (Carbohydrate Polymers, 2025)

Coupling electrodialysis with microbial electrosynthesis enables high-rate, high-titer, and cost-effective acetate production from CO2 - Zeyan Pan; Jinpeng Yu; Yuhan Guo; Wenjie Yin; Hong Zhang; Jiangtao Sha; Xiaona Hu; Kun Guo (Bioresource Technology, 2025)

Spatial assessment of drinking water flavor in China: Revealing regional disparities and underlying drivers - Youwen Shuai; Kejia Zhang; Tuqiao Zhang; Hui Zhu; Sha Jin; Tingting Hu; Zhefan Yu; Xinyu Liang (Water Research, 2025)

Uncovering the future environmental burdens of medical waste disposal in China and mitigation pathways - Yunchang Ding; Qiuxia Zou; Zeguo Yang; Sha Liang; Huijie Hou; Wenbo Yu; Yufei Yang; Huabo Duan; Jiakuan Yang (Resources, Conservation and Recycling, 2025)

Decoding drinking water flavor: A pioneering and interpretable machine learning approach - Youwen Shuai; Kejia Zhang; Tuqiao Zhang; Hui Zhu; Sha Jin; Tingting Hu; Zhefan Yu; Xinyu Liang (Journal of Water Process Engineering, 2025)

The community succession mechanisms and interactive dynamics of microorganisms under high salinity and alkalinity conditions during composting - Qing-Yu Liu; Yu-Xin Wang; Hao-Qun Sha; Hao-Min Zhou; Yue Sun; Jing Su; Ying Mei; Xin Dai; Xiao-Song He (Journal of Environmental Management, 2025)

Environmental credit evaluation policy and enterprise total factor productivity: Evidence from Chinese listed companies - Lianchao Yu; Haobin Sha; Peinan Ji; Kok Fong See (Journal of Environmental Management, 2025)

Highly sensitive aggregation-induced electrochemiluminescence sensor for cadmium detection in Ganoderma lucidum - Zhi-Hong Xu; Xin Weng; Sha-Sha Wang; Ze-Hao Huang; Wen Xu; Wei Xu; Yu Lin; Hang Gao (Food Chemistry, 2025)

Enhancing single-stage partial nitritation-anammox process with airlift inner-circulation and oxygen partition: A novel strategy for treating high-strength ammonium wastewater - Runchu Wei; Zhigang Tang; Sha Wu; Risen Yang; Hanbo Yu; Jing Chen; Jingyi Jiang; Jianhong Jiang; Zhe Kong; Yanxiao Wei; Ali E.A. Elsayed; Hong Chen (Environmental Research, 2025)

Combined skin injury model from airblast overpressure and seawater immersion in rats: establishment, characterization, and mechanistic insights - Jinpeng Du; Zhao Li; Yi Kong; Wei Song; Zhongming Chen; Mengde Zhang; Yuyan Huang; Chao Zhang; Xu Guo; Linhao Hou; Yaxin Tan; Liting Liang; et al. (Journal of Molecular Histology, 2025)

Enhanced phosphorus bioavailability of biochar derived from sewage sludge co-pyrolyzed with K, Ca-rich biomass ash - Xiao Guo; Sha Liang; Zhengkang Zou; Xiaoxiao Xu; Fan Yang; Junda Quan; Xingwu Li; Huabo Duan; Wenbo Yu; Jiakuan Yang (Water Research, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Improvement of stability and antioxidant capacity of peptide - iron complexes by sonication - Dong Lin; Yongqing Zhang; Qinqin Xiong; Liyun Zhang; Sha Cheng; Jia Yu; Mashaal Ahmad; Yalin Ni; Su Xu; Heng Luo (Food Chemistry, 2025)

Lipidomics analysis of adipose depots at differently aged Sunit sheep - Lu Chen; Xige He; Yunfei Han; Yajuan Huang; Jin Li; Jin Li; Xueting Yu; Xueyan Yun; Jindi Wu; Rina Sha; Tungalag Dong; Gerelt Borjigin (Food Chemistry, 2025)

Devosia alba sp. nov., a potential nitrite-reducing bacterium isolated from a mudflat - Sha-sha Qiu; Hong-zhe Hu; Yi-fan Zhuo; Yue Su; Yu-si Yang; Tao Wang; Qi-yun Zheng; Xin-yi Huang; Ailina Yilibao; Can Chen (Current Microbiology, 2025)

Reconciling the Discrepancy in Projected Global Dryland Expansion in a Warming World - Sha Zhou; Bofu Yu (Global Change Biology, 2025)
Continental drying and associated dryland expansion would accelerate environmental degradation and desertification. However, the rate of continental drying commonly assessed with an aridity index is inconsistent with observations and projections of widespread greening and increased global runoff. This raises questions about the accuracy of assessment methods and projections of continental drying and dryland dynamics in a warming world. Here we show that the continental drying trend has been exaggerated because the potential evapotranspiration (PET) and its rate of increase over time are grossly overestimated with the widely used Penman equations. Using an energy‐based PET estimator, we bias correct the aridity index and find considerably weaker and less extensive continental drying (47% of the global land area) than the 61%–65% based on Penman equations. Dryland expansion is projected to occur over only 2.1% of global land area in a high‐emission scenario in the 21st century. Moreover, the corrected aridity index and ecohydrological and hydroclimate projections all show no change in significance consistently in the extent of global drylands based on 32 climate models. These findings resolve the ongoing debate about global dryland expansion and have far‐reaching implications for understanding long‐term changes in the climate system and their impacts on terrestrial ecohydrological processes.

MMP13 as an effective target of an active trifluoromethyl quinazoline compound against osteosarcoma - Chang-hua Zhou; Ting Zhang; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Bi-xue Xu; Heng Luo; Xiao-bin Tian (Toxicology and Applied Pharmacology, 2025)

Bivalve faunal changes in Xunhua Basin shed light on the Late Miocene uplift, cooling and aridification of NE Tibetan Plateau - Jiahao Li; Bowen Song; Tingting Yu; Kexin Zhang; Junliang Ji; Thomas J. Algeo; Jingeng Sha; Sha Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Status and habitat suitability evaluation: A case study of the typical temperate seagrass beds in the Bohai Sea, China - Jingjing Sha; Xudong Liu; Hui Wang; Xiaoli Song; Mengmeng Bao; Qingyun Yu; Guoyi Wen; Miao Wei (Marine Environmental Research, 2025)

Multi-organ toxicity caused by PM2.5 in mice with cardiovascular diseases: The role of PAHs played from the most polluted episodes in China - Jinjin Yu; Jian Sun; Yajing Ma; Xinyi Niu; Ruisi Zhu; Huixin Song; Lingyi Liu; Yuzhi Luo; Songyuan Xia; Jingyu Wang; Lingli Li; Sha Wen; et al. (Journal of Environmental Management, 2025)

Characteristics identification and mitigating potentials of provincial gaseous reactive nitrogen emissions from livestock and poultry breeding systems in China - Shujie Yu; Wencong Yue; Sumei Li; Sha Chen; Peize Wu (Journal of Environmental Management, 2025)

Biomonitoring and food surveillance on heavy metals reveal need for food safety in a coastal region - Xin Zhang; Xiaoqian Yang; Xiaoyue Hu; Zhonghua Meng; Zhigang Yu; Zhan Sun; Ying Zhang; Zhifeng Yang; Sha Li; Jia-Sheng Wang; Qiang Jia; Lanzheng Liu; et al. (Food Research International, 2025)

Synthesis of value-added uridine 5'-diphosphate-glucose from sucrose applying an engineered sucrose synthase counteracts the activity-stability trade-off - Liting Zhao; Zhongbao Ma; Linpei Zhang; Yu Shen; Lei Chen; Youran Li; Sha Xu; Guiyang Shi; Daming Fan; Zhongyang Ding (Food Chemistry, 2025)

Aqueous phase photolysis of 4-nitrocatechol: Reaction kinetics, evolutions of chemical composition, light absorption and oxidation potential - Ruoyuan Lei; Yingying Sha; Haifeng Meng; Yu Huang; Jianhuai Ye; Dan Dan Huang; Yunjiang Zhang; Yun Wu; Yongjie Li; Xinlei Ge (Atmospheric Environment, 2025)

Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Loaded Mir-29-3p Targets AhR to Improve Juvenile Idiopathic Arthritis via Inhibiting the Expression of IL-22 in CD4+ T Cell - Xinyi Wei; Kunpeng Sui; Yuanyuan Peng; Sha Li; Yu Fang; Zhi Chen; Xiao Du; Xue Xie; Haiming Tang; QiuYue Wen; JingWei Li; Meilin He; et al. (Stem Cell Reviews and Reports, 2025)

Design and synthesis of N-aryl-2-trifluoromethyl-quinazoline-4-amine derivatives as potential Werner-dependent antiproliferative agents - Huimin Li; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Jiaomei Wei; Chang You; Kun Liu; Menghan Wang; Xueling Meng; Guangcan Xu; Heng Luo; et al. (Molecular Diversity, 2025)

ENSO-Former: spatiotemporal fusion network based on multivariate and dual-branch transformer for ENSO prediction - Wei Fang; Yu Sha (Climate Dynamics, 2025)

Critical evaluation of extracellular polymeric substances extraction methods: Extraction efficiency, molecular characteristics, and heavy metals binding properties - Bei Ou; Xueyang Hu; Wenbo Yu; Fanhao Meng; Wen Li; Sha Liang; Shushan Yuan; Huabo Duan; Huijie Hou; Keke Xiao (Science of The Total Environment, 2025)

Effects of polyethylene and poly (butyleneadipate-co-terephthalate) contamination on soil respiration and carbon sequestration - Mengyu Liu; Yao Yu; Ying Liu; Sha Xue; Darrell W.S. Tang; Xiaomei Yang (Environmental Pollution, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Selective surface passivation of gold nanoparticles: A strategy for enhanced sensitivity in lateral flow immunoassay - Zongyou Chen; Sha Yu; Shijin Huang; Wei Zhang; Ping Guo; Juan Peng; Yonghua Xiong; Bingfeng Ma; Weihua Lai (Chemical Engineering Journal, 2025)

Apoc1 Knockdown Alleviates High Glucose-induced Oxidative Stress and Apoptosis of Renal Tubular Cells by Binding to Clusterin - Liyin Chai; Zhengyang Liu; Jun Zeng; Li Gong; Sha Xiang; Jing Yu; Haili Sun; Chaolin Wen; Fang Wang; Ning Li; Bingbing Shen; Mei Mei (Cell Biochemistry and Biophysics, 2024)

Comprehensive evaluation of bioavailable phosphorus in biochar synthesized by co-pyrolysis of sewage sludge and straw ash - Xiaoxiao Xu; Zhengkang Zou; Xiao Guo; Sha Liang; Fan Yang; Shuai Chen; Wenbo Yu; Huabo Duan; Shushan Yuan; Jiakuan Yang (Science of The Total Environment, 2024)

Emissions of gaseous nitrous acid (HONO) from diesel trucks: Insights from real-driving emission experiments - Songdi Liao; Zhipeng Tu; Fei Yu; Manni Zhu; Kaiming Sun; Qinge Sha; Xinping Yang; Junyu Zheng (Science of The Total Environment, 2024)

Urine multi-omics markers to predict seizure one day in advance - Wanlin Lai; Leihao Sha; Rui Li; Shan Yu; Ling Jin; Ruiqi Yang; Chao Yang; Lei Chen (Science Bulletin, 2024)

Efficient phosphorus recovery from simulated phosphoric acid wastewater using a tailored dual-module flow electrode capacitive deionization (FCDI) strategy - Fan Yang; Shuai Chen; Sha Liang; Mingxuan Wen; Junda Quan; Xiong Shi; Shushan Yuan; Huabo Duan; Wenbo Yu; Liang Huang; Jiakuan Yang (Resources, Conservation and Recycling, 2024)

Broad-spectrum detection of benzimidazoles with lateral flow immunoassay: A computational chemistry-assisted hapten design strategy and explore of molecular recognition mechanism - Jiaqi Yin; Sha Yu; Xi Mei; Zongyou Chen; Juan Peng; Weihua Lai (Journal of Hazardous Materials, 2024)

Nanozyme coating-gated multifunctional COF composite based dual-ratio enhanced dual-mode sensor for highly sensitive and reliable detection of organophosphorus pesticides in real samples - Shao-Hua Wen; Hengyuan Zhang; Sha Yu; Junping Ma; Jun-Jie Zhu; Yuanzhen Zhou (Journal of Hazardous Materials, 2024)

Understory plant diversity supports the delivery of ecosystem multifunctionality on the Loess Plateau: A comparative of plantations and natural forests - Guoliang Sha; Huan Yu; Yuxuan Chen; Kang Ren; Pengcheng Xin; Xin Guo; Jing Xiao; Yanchao Fu (Journal of Environmental Management, 2024)

Comparison of Pb adsorption and transformation behavior induced by chicken manure and its DOM in contaminated soil - Yue Jiang; Wei Yang; Jiaqi Zhang; Xuesheng Liu; Yu Jin; Sha Li; Juanjuan Qu; Wei Wang (Journal of Environmental Chemical Engineering, 2024)

Effects of LDPE and PBAT plastics on soil organic carbon and carbon-enzymes: A mesocosm experiment under field conditions - Xinkai Jia; Yu Yao; Gaowei Tan; Sha Xue; Mengjuan Liu; Darrell W.S. Tang; Violette Geissen; Xiaomei Yang (Environmental Pollution, 2024)

The role of the pulp and paper industry in achieving net zero U.S. CO2 emissions in 2050 - Molly Charles; Kanishka B. Narayan; Jae Edmonds; Sha Yu (Energy and Climate Change, 2024)

Carbon management technology pathways for reaching a U.S. Economy-Wide net-Zero emissions goal - Matthew Binsted; Ellie Lochner; Jae Edmonds; José Benitez; John Bistline; Morgan Browning; Francisco De La Chesnaye; Jay Fuhrman; Leonard Göke; Gokul Iyer; Kathleen Kennedy; Page Kyle; et al. (Energy and Climate Change, 2024)

Unveiling amoxicillin photocatalytic decontamination utilizing CuFe2O4/CuS core-shell heterostructure-integrated peroxymonosulfate activation: Mechanism insights, aquatic hazard assessment, and environmental implementation - Chao Lei; Mingli Ye; Jun Tang; Cun Yu; Sha Yu (Journal of Water Process Engineering, 2024)

Adverse effect of TWPs on soil fungi and the contribution of benzothiazole rubber additives - Chu Peng; Yuan Wang; Xiaoyu Sha; Mengxi Li; Xinling Wang; Jiao Wang; Yu Wang; Chunguang Liu; Lei Wang (Journal of Hazardous Materials, 2024)

In vitro digestion and fecal fermentation of Tremella fuciformis exopolysaccharides from basidiospore-derived submerged fermentation - Yan Fang; Qi Zhang; Caiyuan Yu; Xiaoqi Xu; Peng Lei; Hong Xu; Sha Li (Food Research International, 2024)

Re3P4@C/TiO2 Ohmic junction Boosts charge carrier separation for photocatalytic hydrogen evolution - Jun-Wei Ji; Li-Jing Zhang; Wen-Jing Yi; Yu Wang; Jing-Huo Chen; Xin-Zheng Yue; Sha-Sha Yi (Chemical Engineering Journal, 2024)

Green chemistry closed-loop: Photocatalytic cleavage lignin β-O-4 bond utilizing visible light by Bi2O3/Bi2WO6 in deep eutectic solvent at room temperature - Chengcheng Suo; Jintao Yu; Jifang Zhang; Wei Li; Sha Luo; Chunhui Ma; Shouxin Liu (Biomass and Bioenergy, 2024)

Construction of 2-azidacetic acid functionalized high-crystallinity fluorescent covalent organic framework: Applications in mitoxantrone and Fe3+ sensing and adsorption - Yuemeng Zou; Famin Ke; Yulian Yang; Dandan Wang; Mingyue Wang; Qiuyi Liu; Sha Yu; Lingling Li; Yue Lan; Xilin Yang; Xiurong Guo; Xiang Li; et al. (Chemosphere, 2024)

Decarbonization pathways for Korea's industrial sector towards its 2050 carbon neutrality goal - Hanju Lee; Haewon McJeon; Sha Yu; Yang Liu; Hanwoong Kim; Jiyong Eom (Journal of Cleaner Production, 2024)

A new glycoprotein from pigeon egg: Study on its structure and digestive characteristics - Yu Xiao; Zeyun Zhao; Tao Zhang; Xiaoqi Xu; Khan Anik; Yibin Qiu; Zheng Xu; Sha Li; Hong Xu (Food Research International, 2024)

Glycoprotein from selenium-enriched yam activates immune cells and enhances intestinal immunity via the NF-κB signaling pathway - Siqi Wang; Jinjin Yu; Lili Zhou; Yuzhi Luo; Lingyi Liu; Sha Wen; Lingli Li; Yajing Ma; Huixin Song; Song Ming; Weifeng Li; Xiaofeng Niu (Food Bioscience, 2024)

Parametric analysis on mechanical performance and additional reinforcement design method of reinforced concrete chimneys with openings - Zhi-Qian Dong; Gang Li; Song-Ke Zhang; Sha-Yi Wang; Ding-Hao Yu; Zeng-Bo Yao; Chun-Gang Liu; Mei Yang (Bulletin of Earthquake Engineering, 2024)

Physical basis of the potential evapotranspiration and its estimation over land - Sha Zhou; Bofu Yu (Journal of Hydrology, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Engineering Au-Pt atomic alloy cocatalysts for enhanced H2 production from photo-reforming of lignocellulosic biomass wastes - Fangjie Ding; Hongbo Yu; Renyong Tu; Sha Li; Lin Chen; Bing Li; Jianzhong Guo; Chunzheng Wu (Chemical Engineering Journal, 2024)

Strong light-trapping probes with high antibody activity for sensitive detecting FB1 by “turn-on” lateral flow immunoassay - Sha Yu; Gan Zhang; Liming Hu; Huayuan Ji; Jiawei Chen; Juan Peng; Weihua Lai (Chemical Engineering Journal, 2024)

Composition effects on equilibrium oxygen isotope fractionation factors between garnets and quartz/calcite/olivine: Implication from vibration frequencies of garnets at high temperatures and high pressures - Xi Zhu; Guangchen Chen; Yu Ye; Zhengrong Wang; Wei Du; Qingbo Wang; Sha Wang; Yancheng Hu; Yunfan Miao; Zhen Wu; Dan Liu (Chemical Geology, 2024)

Fabrication of high mechanical strength and high porosity PVDF isoporous membranes based on inverse opal photonic crystals - Sha Fan; Yu Wang; Xinyi Hong; Gaofeng Liu; Chengcai Li; Hailin Zhu; Bin Yu; Guojin Liu (Journal of Water Process Engineering, 2024)

Enhancement of efficient molecular biology tools for Tremella fuciformis spore - Caiyuan Yu; Yuanwei Sun; Chunkai Yang; Yan Fang; Qi Meng; Yibin Qiu; Peng Lei; Hong Xu; Qi Zhang; Sha Li (Food Bioscience, 2024)

Innovative insights into dry fermented sausages flavor: Unraveling the impact of varied lactobacillus genera-driven fermentation - Sha-sha Zheng; Ying-ying Hu; Li-jun Tan; Liu Yang; Chun-yu Wang; Bao-cai Xu (Food Bioscience, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

SNX14 inhibits autophagy via the PI3K/AKT/mTOR signaling cascade in breast cancer cells - Sha Lv; Hongyan Jiang; Lingyan Yu; Yafei Zhang; Liangliang Sun; Junjun Xu (Journal of Molecular Histology, 2024)

Are vacuolar dynamics crucial factors for plant cell division and differentiation? - Ya-Nan Wu; Jin-Yu Lu; Sha Li; Yan Zhang (Plant Science, 2024)

Interannual Variation of Summer Sea Surface Salinity in the Dotson–Getz Trough, West Antarctica - Lu-Sha Yu; Hailun He; Hengling Leng; Xiaohui Chen (Journal of Marine Science and Engineering, 2024)
In this study, we explore the interannual variability of Sea Surface Salinity (SSS) in the Dotson–Getz Trough located in West Antarctica, focusing on the month of February. Utilizing the oceanic analysis product EN4, we first validate the EN4 SSS with data from a singular ship-based survey, and then delve into potential factors that may influence SSS, with a particular emphasis on surface freshwater flux, sea ice concentration (SIC), and also the surface stress curl, which will induce upwelling via Ekman transport to affect the SSS. Our findings primarily indicate a link between SSS and sea ice concentration, showcasing a negative correlation where the peak (average) coefficient is around −0.6 (−0.4), further affirming the substantial interannual variability of SSS in this region.

External carbon source as a viable tool for controlling antibiotics and antibiotic resistance genes (ARGs) in effluent: Influence on antibiotic removal and ARGs dissemination - Yining Qu; Peng Li; Yuxue Liu; Sha Dai; Yu Xie; Yiliang He (Journal of Environmental Management, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

High efficiency triethylamine gas sensor based on SmVO4 nano octahedron granules - Cheng Yu Xu; Shu Yi Ma; Tian Yuan Dong; Ji Ming Liu; Jin Sha Wei; Hong Tao Jiang; Ping Ni; Ge Ge Fan; Jia Yun Guo (Journal of Environmental Chemical Engineering, 2024)

Tannic acid mediated hollow biocatalytic zeolitic imidazolate frameworks as a “three-in-one” label for enhancing the sensitivity of fluorescence immunosensor - Xudong Jing; Xinliu Tan; Zhou Yu; Yanyan Tang; Sha Yu; Gan Zhang; Yonghua Xiong; Daofeng Liu; Weihua Lai (Chemical Engineering Journal, 2024)

Boosting electrocatalytic activity of Ru for hydrogen evolution through engineering Ru on multiple interfaces of 1T-MoS2 and carbon - Changyi Xu; Huizhen Yu; Huamei Huang; Wanchun Huang; Sha Li; Yinghuan Cao; Haifeng Lu; Guimei Li; Yejin Li; Xiaokun Li; Youlin Zhang; Wei Chen (Chemical Engineering Journal, 2024)

Draconibacterium aestuarii sp.nov., a Glycolipid-Producing Bacterium Isolated from Tidal Flat Sediment and Emended Description of the Genus Draconibacterium - Jia-Yan Wang; Sha-Sha Qiu; Yue Su; Wei-Yu Pan; Tao Wang; Wen-Wu Zhang; Ge-Yi Fu; Min Wu (Current Microbiology, 2024)

Di-n-butyl phthalate induces toxicity in male fetal mouse testicular development by regulating the MAPK signaling pathway - Xinwei Wan; Xudong Cui; Xiang Wang; Mingyang Feng; Shinan Wei; Jia Yu; Sha Cheng; Heng Luo; Jianxin Hu (Toxicology and Applied Pharmacology, 2024)

Enhancing phosphorus removal by novel porous concrete fabricated with alkali-activated aggregate derived from industrial solid wastes - Junda Quan; Xilong Li; Sha Liang; Guang Hu; Xingwu Li; Wenbo Yu; Shushan Yuan; Huabo Duan; Jingping Hu; Huijie Hou; Xiong Shi; Jiakuan Yang (Resources, Conservation and Recycling, 2024)

Designed synthesis N-doped sulfonated bifunctional catalyst for efficient 5-hydroxymethylfurfural production: A pyridinic N-triggered proton-shift mechanism at basic sites - Yu Yin; Yabo Qi; Chunhui Ma; Zhenwei Wu; Wei Li; Sha Luo; Shouxin Liu (Fuel, 2024)

Preconditioning exercise reduces brain damage of ischemic stroke in rats via PI3K–AKT pathway by bioinformatic analysis - Kai Li; Zhen-Kun Gao; Yi-Sha Guo; Xin-Ya Shen; Yu Han; Mei Yuan; Xia Bi (Experimental Brain Research, 2024)

Genome-wide identification and quantification of salinity-responsive Na+/K+-ATPase α-subunits in three salmonids - Yue Su; Shuang-En Yu; Yong-Xu Sun; Liang Zhang; Yue Tan; Yu-Yang Zhang; Shuo Wang; Yan-Gen Zhou; Li-Sha Hu; Yun-Wei Dong (Aquaculture, 2024)

Uptake and accumulation of di(2-ethylhexyl) phthalate (DEHP) in a soil-ginseng system and toxicological mechanisms on ginseng (Panax ginseng C.A. Meyer) - Yu-shun Lu; Zheng-bo Liu; Yan-yang Xu; Ji-yue Sha; Di Qu; Yin-shi Sun (Science of The Total Environment, 2024)

Advancements in the loop-mediated isothermal amplification technique for the rapid detection of plant viruses in various crops - Ruizuo Fu; Yu Sha; Xiangbin Xu; Song-Bai Liu (Physiological and Molecular Plant Pathology, 2024)

LA-ICPMS in situ U Pb dating of skarn garnet from the Tongling ore district of eastern China - Ting Liang; Shao-Bing Zhang; Xiao-Yong Yang; Zhen-Xin Li; Xing-Yu Yao; Yu Wang; Sha-Sha Liu (Lithos, 2024)

Natural and anthropogenic dissolved organic matter in landfill leachate: Composition, transformation, and their coexistence characteristics - Jing Zheng; Xian-Ge Wang; Yue Sun; Yu-Xin Wang; Hao-Qun Sha; Xiao-Song He; Xiao-Jie Sun (Journal of Hazardous Materials, 2024)

Preparation and evaluation of liquorice (Glycyrrhiza uralensis) and ginger (Zingiber officinale) kombucha beverage based on antioxidant capacities, phenolic compounds and sensory qualities - Ruo-Gu Xiong; Dan-Dan Zhou; Jin Cheng; Si-Xia Wu; Adila Saimaiti; Si-Yu Huang; Qing Liu; Ao Shang; Hua-Bin Li; Sha Li (International Journal of Gastronomy and Food Science, 2024)

In vitro digestion and fecal fermentation of selenocompounds: impact on gut microbiota, antioxidant activity, and short-chain fatty acids - Shuojia Liang; Junlei Yu; Meng Zhao; Sha Chen; Xiang Lu; Fayin Ye; Jia Chen; Guohua Zhao; Lin Lei (Food Research International, 2024)

Population genetic structure and implication for adaptive differentiation of the snail (Gastropoda, Provannidae) in deep‐sea chemosynthetic ecosystems - Yu Zhang; Jiao Cheng; Zhongli Sha; Min Hui (Zoologica Scripta, 2024)
The snail Provanna glabra is a dominant species inhabiting both hydrothermal vents and cold seeps of the Northwest Pacific Ocean. The genetic diversity and population structure of the snail from the hydrothermal vents of Okinawa Trough and a methane seep in the South China Sea were investigated using mitochondrial cytochrome c oxidase subunit I (COI) and genome‐wide single nucleotide polymorphisms (SNPs). A total of 28,805 SNPs were screened based on 2b‐RAD sequencing. Substantial genetic differences between vent and seep populations were identified based on the two datasets with F ST = 0.753 (COI) and F ST = 0.109 (SNPs), respectively. The results of phylogenetic tree, ADMIXTURE and principal component analysis jointly supported the population differentiation. Outlier detection confirmed the local adaptation of P. glabras populations, and the annotation of these outliers revealed that they were closely associated with processes of signal transduction, immunity, DNA repair, transposable elements and biological development. The genetic divergence observed between hydrothermal vent and methane seep P. glabra populations might be induced by the geographic barrier, limited dispersal ability and natural selection imposed by local environmental pressures from different deep‐sea habitats, e.g. chemical composition, temperature and microbes. These results provide a genetic basis for the microevolution of snails inhabiting deep‐sea chemosynthetic ecosystems.

PLZF protein forms a complex with protein TET1 to target TCF7L2 in undifferentiated spermatogonia - Xiaomin Du; Donghui Yang; Xiuwei Yu; Yudong Wei; Wenbo Chen; Yuanxin Zhai; Fanglin Ma; Mengfei Zhang; Shicheng Wan; Yunxiang Li; Xinchun Yang; Aili Aierken; et al. (Theriogenology, 2024)

Antiferromagnetic imaging via ptychographic phase retrieval - Jizhe Cui; Haozhi Sha; Wenfeng Yang; Rong Yu (Science Bulletin, 2024)

Enhancement of fermented sausage quality driven by mixed starter cultures: Elucidating the perspective of flavor profile and microbial communities - Sha-sha Zheng; Chun-yu Wang; Ying-ying Hu; Liu Yang; Bao-cai Xu (Food Research International, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

Selaginellin derivatives from Selaginella tamariscina and evaluation for anti-breast cancer activity - Jing Wen; Dong-Mei Sha; Xiao-Yong He; Yu-Han Tian; Shuai-Cong Ni; Bin He; Yuan Liu; Xin-Jia Yan (Phytochemistry, 2024)

Tandem mass spectrometry tag proteomic analysis of milk and colostrum of Guanzhong dairy goat - Chen Lu; Yu Mengqi; Yuan Yuxin; Qu Yingxin; Sha Riakang; Ren Xinyang; Li Guang (International Dairy Journal, 2024)

Quantifying threshold and scale response of urban air and surface temperature to surrounding landscapes under extreme heat - Xinyu Bai; Zhaowu Yu; Benyao Wang; Yanting Zhang; Siqi Zhou; Xiaohan Sha; Siheng Li; Xihan Yao; Xiaolei Geng (Building and Environment, 2024)

High Lewis acidity catalyst for direct depolymerization of microcrystalline cellulose to 5- hydroxymethylfurfural: Reaction optimization by central composite design - Yu Yin; Chunhui Ma; Wei Li; Sha Luo; Zhanshuo Zhang; Shouxin Liu (Biomass and Bioenergy, 2024)

Comparative transcriptomic and lipidomic analysis of oleic environment adaptation in Saccharomyces cerevisiae: insight into metabolic reprogramming and lipid membrane expansion - Yi Shen; Xia Ke; Zi-Hao Pan; Li-Sha Cao; Zhi-Qiang Liu; Yu-Guo Zheng (Systems Microbiology and Biomanufacturing, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

The effect of aperiodic components in distinguishing Alzheimer’s disease from frontotemporal dementia - Zhuyong Wang; Anyang Liu; Jianshen Yu; Pengfei Wang; Yuewei Bi; Sha Xue; Jiajun Zhang; Hongbo Guo; Wangming Zhang (GeroScience, 2023)

Sludge-derived iron-carbon material enhancing the removal of refractory organics in landfill leachate: Characteristics optimization, removal mechanism, and molecular-level investigation - Xinyue Chen; Sha Liang; Shuangyi Tao; Wenbo Yu; Shushan Yuan; Sifeng Jian; Nianhong Wan; Yuwei Zhu; Shijie Bian; Yuan Liu; Liang Huang; Huabo Duan; et al. (Science of The Total Environment, 2023)

Dietary supplementation with American ginseng dietary fiber ameliorates intestinal mucosal barrier injury in immunosuppressed mice - Jiyue Sha; Zhengbo Liu; Hongxia Yu; Xiaohui Huo; Jiajia Wang; Yuanyuan Duan; Wei Li; Di Qu; Zhiman Li; Jianbo Chen; Xueqing Li; Yinshi Sun (Food Bioscience, 2023)

Recent progress on atomic-scale modulation of single-atom-based catalysts for electrocatalytic CO2 reduction - Yingjie Liu; Sha Bai; Qian Li; Zhaohui Wu; Tianyang Shen; Jinfeng Chu; Yu-Fei Song (Chemical Engineering Journal, 2023)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Dietary nano-selenium improves health of liver and intestine of grass carp Ctenopharyngodon idella after overwintering - Limin Ye; Sha Liu; Xiaotian Zhang; Chi Wang; Pengju Li; Cheng Zhang; Hong Ji; Haibo Yu (Animal Feed Science and Technology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Numerical simulation to optimize passive aeration strategy for semi-aerobic landfill - Shuai Guo; Wenbo Yu; Hongyang Zhao; Changfei Lai; Shijie Bian; Pan Jin; Sha Liang; Shushan Yuan; Liang Huang; Songlin Wang; Huabo Duan; Feifei Wang; et al. (Waste Management, 2023)

Developing a model-ready highly resolved HONO emission inventory in Guangdong using domestic measured emission factors - Xiaohong Yin; Feng Tang; Zhijiong Huang; Songdi Liao; Qinge Sha; Peng Cheng; Menghua Lu; Zhen Li; Fei Yu; Yuanqian Xu; Min Shao; Junyu Zheng (Science of The Total Environment, 2023)

Enhanced sludge dewatering by PDMDAAC coupled with Fenton-like reaction initiated by Fe-rich sludge biochar with in-situ generation of H2O2: Fe/C structure as an electron shuttle - Shuangyi Tao; Sha Liang; Xingyue Chen; Yuwei Zhu; Wenbo Yu; Huijie Hou; Jingping Hu; Keke Xiao; Shushan Yuan; Jiakuan Yang (Resources, Conservation and Recycling, 2023)

Hierarchical wood cells impose well-textured carbon nanotubes with cobalt single atoms: Bioinspired construction and application in zinc–air battery - Yangyang Chen; Ying Wu; Lei Li; Yu Liao; Sha Luo; Han Xu; Yiqiang Wu; Yan Qing (Chemical Engineering Journal, 2023)

A superstable, flexible, and scalable nanofluidic ion regulation composite membrane - Lianmeng Si; Yihan Wu; Hong Xiao; Wensi Xing; Rui Song; Yiju Li; Sha Wang; Xu Liang; Wenshan Yu; Jianwei Song; Shengping Shen (Science Bulletin, 2023)

Assessing the efficiency of ozone-based advanced drinking water treatment processes in removing antibiotics and antibiotic-resistant genes: Pilot-scale research - Gezi Li; Bolin Li; Mingxing Yu; Jun Wang; Longwei Jiang; Ying Yu; Xueni Sha; Xiaoman He; Zhi Zhou (Journal of Water Process Engineering, 2023)

Mowing increased plant diversity but not soil microbial biomass under N-enriched environment in a temperate grassland - Qiushi Ning; Liangchao Jiang; Guoxiang Niu; Qiang Yu; Jushan Liu; Ruzhen Wang; Sha Liao; Jianhui Huang; Xingguo Han; Junjie Yang (Plant and Soil, 2023)

Revealing the roles of chemical communication in restoring the formation and electroactivity of electrogenic biofilm under electrical signaling disruption - Qian Zhu; Dingkang Qian; Mengjiao Yuan; Zhen Li; Ziming Xu; Sha Liang; Wenbo Yu; Shushan Yuan; Jiakuan Yang; Huijie Hou; Jingping Hu (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Studying the effect of light intensity on the photosynthetic mechanism of pepper leaf yellowing mutants by proteomics and phosphoproteomics - Lianzhen Mao; Yunhua Dai; Yu Huang; Sha Yang; Hao Sun; Yao Zhou; Ying Sun; Bozhi Yang; Xuexiao Zou; Zhoubin Liu (Plant Science, 2023)

Exploring global carbon market link mechanism: Efficiency evaluation in the context of carbon neutrality - Hanying Jiang; Jiachen Wang; Sha Yu; Xinzhu Zheng; Can Wang (Journal of Cleaner Production, 2023)

Factor contribution to soil carbon and nitrogen accumulation after vegetation restoration on the Loess Plateau, China - Yuxuan Chen; Guoliang Sha; Tianxing Wei; Kang Ren; Xin Guo; Huan Yu; Shan Jiang (Ecological Engineering, 2023)

Cardanol-based epoxy vitrimer/carbon fiber composites with integrated mechanical, self-healing, reprocessable, and welding properties and degradability - Yun Hu; Shanyuan Tong; Ye Sha; Juan Yu; Lihong Hu; Qin Huang; Puyou Jia; Yonghong Zhou (Chemical Engineering Journal, 2023)

Responses of soil microbial communities to vegetation restoration on the Loess Plateau of China: A meta-analysis - Guoliang Sha; Yuxuan Chen; Tianxing Wei; Xin Guo; Huan Yu; Shan Jiang; Pengcheng Xin; Kang Ren (Applied Soil Ecology, 2023)

Acer truncatum leaves reduce lipid accumulation and improve liver and intestine health of grass carp (Ctenopharyngodon idella) fed with high-fat diet - Limin Ye; Xiaotian Zhang; Chi Wang; Sha Liu; Pengju Li; Cheng Zhang; Qinfeng Gao; Hong Ji; Haibo Yu (Aquaculture, 2023)

Surface chemistry regulation of nanoparticle coatings on activated carbons for rapid and long-lasting adsorption of organic pollutants - Xuan Jiao; Xingyu Liu; Yanzheng Ji; Sha Yang; Shu Yang; Pan Feng; Dewen Sun; Qianping Ran; Wei Liu; Xinquan Yu; Youfa Zhang (Journal of Cleaner Production, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Evaluation the role of soluble microbial products for denitrification sludge characteristic under starvation stress - Qian-Qian Zhang; Yan Yu; Jin-Ze Liu; Wen-Jing Fu; Jin-Yang Quan; Ying Chen; Jian-Qiang Zhao; Sha Wang; Ren-Cun Jin (Science of The Total Environment, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

Efficiently activating peroxymonosulfate by CoFe-LDHs/MoS2 for rapid degradation of tetracycline - Jingyang Li; Haiyu Cao; Hongying Qi; Yuexiang Li; Sha Zhu; Xue Ye; Jintao Zhang; Zifeng Yu; Jiao Zhu; Xin Zhao (Journal of Water Process Engineering, 2023)

Effect of lead, calcium, iron, zinc, copper and magnesium on anemia in children with BLLs ≥ 100 μg/L - Xiaoyu Yu; Liang Xiong; Sha Zhao; Zhengqiu Li; Shiting Xiang; Yuhan Cao; Changci Zhou; Jie Dong; Jun Qiu (Journal of Trace Elements in Medicine and Biology, 2023)

The expansion of evergreen and deciduous shrubs changed the chemical characteristics and biological community of alpine meadows soil - Yu Zhou; Moyu Sha; HuiQin Jin; Lifeng Wang; Jian Zhang; Zhenfeng Xu; Bo Tan; Lianghua Chen; Lixia Wang; Sining Liu; Jiujin Xiao; Chengming You; et al. (European Journal of Soil Biology, 2023)

Sn2+/Mn2+ co-doped germanate glass with quasi-sunlight spectrum visible-emission and its high-quality w-LED application - Yuhang Zhang; Baojiu Chen; Xizhen Zhang; Yongze Cao; Jinsu Zhang; Sai Xu; Xiangping Li; Hongquan Yu; Duan Gao; Xuezhu Sha; Li Wang; Xin Chen; et al. (Chemical Engineering Journal, 2023)

Hyper non-CG methylation of expanded plant disease resistance NLR genes - Qianqian Cao; Shichao Wang; Huizhen Ma; Sha Luo; Hai He; Yu Zhang (Plant Cell Reports, 2023)
Key message We explored the phylogenomics and methylomics of NLR genes in 41 plant species and found that highly duplicated plant NLR genes are hyper methylated in non-CG context.

miR-671-5p Upregulation Attenuates Blood–Brain Barrier Disruption in the Ischemia Stroke Model Via the NF-кB/MMP-9 Signaling Pathway - Ling Deng; Jiyu Zhang; Sha Chen; Yu Wu; Xiaomei Fan; Tianrui Zuo; Qingwen Hu; Lu Jiang; Shaonan Yang; Zhi Dong (Molecular Neurobiology, 2023)

Novel PbO@C composite material directly derived from spent lead-acid batteries by one-step spray pyrolysis process - Wenhao Yu; Mingyang Li; Sha Liang; Qi Xu; Peiyuan Zhang; Huijie Hou; Jingping Hu; Jiakuan Yang (Waste Management, 2023)

Functionalized graphitic carbon nitride based catalysts in solar-to-chemical conversion for hydrogen peroxide production - Chao Liang; Xue-Min Wang; Wei Liu; Hui-Yun Liu; Da-Wei Huang; Yuan-Zheng Zhang; Kai-Hang Zhang; Li-Sha Jiang; Yu-Yu Jia; Cheng-Gang Niu (Chemical Engineering Journal, 2023)

Pulses outweigh cumulative effects of water diversion from river to lake on lacustrine phytoplankton communities - Jiangyu Dai; Haifei Sha; Xiufeng Wu; Shiqiang Wu; Yu Zhang; Fangfang Wang; Ang Gao; Jiayi Xu; Fuwei Tian; Senlin Zhu; Mariusz Ptak (Environmental Geochemistry and Health, 2023)

2,4-Dinitrotoluene (2,4-DNT) exposure induces liver developmental damage and perturbs lipid metabolism and oxygen transport gene expression in zebrafish (Danio rerio) - Liangxia Su; Hang Sha; Jun Liu; Le Yu; Huanhuan Li; Rui Wang (Environmental Science and Pollution Research, 2023)

A sustainable strategy for recovery of phosphorus as vivianite from sewage sludge via alkali-activated pyrolysis, water leaching and crystallization - Liang Yang; Xiao Guo; Sha Liang; Fan Yang; Mingxuan Wen; Shushan Yuan; Keke Xiao; Wenbo Yu; Jingping Hu; Huijie Hou; Jiakuan Yang (Water Research, 2023)

Recent progress on highly efficient removal of heavy metals by layered double hydroxides - Tong He; Qian Li; Tong Lin; Jiaxin Li; Sha Bai; Sai An; Xianggui Kong; Yu-Fei Song (Chemical Engineering Journal, 2023)

Polysulfides manipulation: Constructing g-C3N4 networks encapsulated into natural wood fibers for high-performance lithium–sulfur batteries - Yangyang Chen; Ying Wu; Lei Li; Yu Liao; Sha Luo; Yiqiang Wu; Yan Qing (Chemical Engineering Journal, 2023)

Quantifying tree canopy coverage threshold of typical residential quarters considering human thermal comfort and heat dynamics under extreme heat - Yingnan Li; Dongli Lin; Yuhan Zhang; Zipeng Song; Xiaohan Sha; Siqi Zhou; Cen Chen; Zhaowu Yu (Building and Environment, 2023)

Interannual variation of summer sea surface temperature in the Amundsen Sea, Antarctica - Lu-Sha Yu; Hailun He; Hengling Leng; Hailong Liu; Pengfei Lin (Frontiers in Marine Science, 2023)
This paper investigates the interannual variability of January sea surface temperature (SST) in the Amundsen Sea (AS) during the period 1982–2022. SST in the Pine Island Bay (PIB) is found to exhibit the most significant interannual variation, with a standard deviation up to 0.6°. Composite analysis indicates that, in warmer years, the January SST at PIB is approximately 1° higher on average than that in cooler years, and its variation in warmer (cooler) years corresponds to lower (higher) sea ice concentration (SIC) and more (less) surface heat flux; the latter factor is primarily influenced by the albedo of SIC. Further analysis suggests that variability in January SIC is largely dominated by northward sea ice motion during the previous November (r = −0.82), which is consistent with the presence of a contemporaneous northerly 10 m wind anomaly trigged by the Amundsen Sea Low (ASL). The ASL-associated northerly wind anomaly drives northward sea ice motion, reduces SIC, and thus increases the downward heat flux that ultimately results in warmer SST, and vice versa. This study identifies the possible mechanism of anomalous January SST in the PIB, which could provide an important clue for seasonal forecasts of summer SST in the AS.

Quality assessment of variable collagen tissues of sea cucumber (Stichopus japonicus) body wall under different heat treatment durations by label-Free proteomics analysis - Yi-Zhen Huang; Yi-Sha Xie; Yan-Xin Li; Mei-Yu Zhao; Na Sun; Hang Qi; Xiu-Ping Dong (Food Research International, 2023)

Pioneer tree species accumulate higher neighbourhood diversity than late-successional species in a subtropical forest - Fanhua Kong; Xiaorong Chen; Minhua Zhang; Yu Liu; Sha Jiang; Ryan A. Chisholm; Fangliang He (Forest Ecology and Management, 2023)

Effects of diflubenzuron on shrimp (Neocaridina palmata) in freshwater systems dominated by submerged plant (Ceratophyllum demersum) - Daoshuai Huang; Shaonan Li; Yu Lu; Meng Sha; Jiaxin Li (Chemosphere, 2023)

A self-circulating electro-fenton-like process over Fe3O4–CaO2 cathode for highly efficient degradation of levofloxacin - Yangyang Bai; Xiaoqin Sun; Yuan Dang; Sha Yu; Jun-Jie Zhu; Yuanzhen Zhou (Chemosphere, 2023)

Insights into leachate reduction in landfill with different ventilation Rates: Balance of Water, waste physicochemical Properties, and microbial community - Pan Jin; Shijie Bian; Wenbo Yu; Shuai Guo; Changfei Lai; Lixin Wu; Hongyang Zhao; Keke Xiao; Sha Liang; Shushan Yuan; Liang Huang; Songlin Wang; et al. (Waste Management, 2023)

Genomic analysis of Marinimicrobium sp. C6131 reveals its genetic potential involved in chitin metabolism - Yan-Ru Dang; Xiao-Yu Zhang; Sha-Sha Liu; Ping-Yi Li; Xue-Bing Ren; Qi-Long Qin (Marine Genomics, 2023)

Heterogeneous driving effects of middle-class expansion on carbon emissions in various regions of China: A structural path decomposition analysis - Ju Wang; Liyuan Wei; Jian Zuo; Sha Peng; Shuxia Yu; Ling Wang; Chang Chen; Zhen Wang (Journal of Cleaner Production, 2023)

Risk assessment of 3-monochloropropane-1,2-diol esters through dietary exposure from edible oils for the Zhejiang population in China by Monte Carlo simulation - Liqun Zhang; Pinggu Wu; Xiaoling Xiang; Huali He; Sha Yu (Food Additives & Contaminants: Part A, 2023)

Isolation, characterization and functional validation of a soybean transcription factor, GmDof4.2 improves drought tolerance in transgenic tobacco - Ying Zhai; Jiongxin Chen; Jiaqi He; Jun Zhang; Wei Sha; Haiwei Yu; Yan Zhao; Tianyi Ma; Tianguo Sun; Meijuan Zhang; Shanshan Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

VOC emission caps constrained by air quality targets based on response surface model: A case study in the Pearl River Delta Region, China - Ya'nan Hu; Bowen Shi; Xin Yuan; Chuanzeng Zheng; Qing'e Sha; Yufan Yu; Zhijiong Huang; Junyu Zheng (Journal of Environmental Sciences, 2023)

In-situ growth of Ni(OH)2 nanoplates on highly oxidized graphene for all-solid-state flexible supercapacitors - Xueli Wu; Fan Zeng; Xianyin Song; Xuefeng Sha; Hongtao Zhou; Xingang Zhang; Zhi Liu; Minghao Yu; Changzhong Jiang (Chemical Engineering Journal, 2023)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

MilR3, a unique SARP family pleiotropic regulator in Streptomyces bingchenggensis - Yu-Si Yan; Yun-Qi Yang; Li-Sha Zhou; Ling Zhang; Hai-Yang Xia (Archives of Microbiology, 2022)

Phylogenetic analyses, morphological studies, and muscarine detection reveal two new toxic Pseudosperma (Inocybaceae, Agaricales) species from tropical China - Li-Na Zhao; Wen-Jie Yu; Lun-Sha Deng; Jian-Hua Hu; Yu-Peng Ge; Nian-Kai Zeng; Yu-Guang Fan (Mycological Progress, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

A risk-based decision model for rainwater resource supply in forward contracts - Yu Zhang; Haifei Sha; Xiufeng Wu; Shiqiang Wu; Jiangyu Dai; Bin Xu; Lei Yu; Qianqian Yang (Water Resources Management, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Biomarker responses and histological damage in the gill, liver, and gonad of Cyprinus carpio with benzo(a)pyrene exposure - Weilai Sha; Fengsen Cai; Yu Li; Ying Wang; Chunchen Liu; Renjun Wang; Peike Gao (Environmental Science and Pollution Research, 2021)

Therapeutic Potential of Cytokines in Demyelinating Lesions After Stroke - Yi-Sha Guo; Mei Yuan; Yu Han; Xin-Ya Shen; Zhen-Kun Gao; Xia Bi (Journal of Molecular Neuroscience, 2021)

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

EEG-Based Anxious States Classification Using Affective BCI-Based Closed Neurofeedback System - Chao Chen; Xuecong Yu; Abdelkader Nasreddine Belkacem; Lin Lu; Penghai Li; Zufeng Zhang; Xiaotian Wang; Wenjun Tan; Qiang Gao; Duk Shin; Changming Wang; Sha Sha; et al. (Journal of Medical and Biological Engineering, 2021)

Carbon isotope variations of modern soils in the eastern margin of the Tibetan Plateau and their controlling factors - Lin Qi; Yan-song Qiao; Zong-xiu Liu; Sha-sha Peng; Yu Cheng; Yan Wang; Xu-jiao Zhang; Ming-zhong Tian; Shuai-bin Yang; Wen-bin Bai (Journal of Mountain Science, 2021)

A novel acid polysaccharide from Boletus edulis: extraction, characteristics and antitumor activities in vitro - Ting Meng; Sha-sha Yu; Hai-yu Ji; Xiao-meng Xu; An-jun Liu (Glycoconjugate Journal, 2021)

Detrital-zircon U–Pb geochronology of Jurassic sandstones in North China Craton (Daqingshan area, China): new constraints on provenance and tectonic implications - Minjie Zhang; Sumei Zhang; Jinyong Choi; Yanqiu Yu; Xinbo Zhang; Sha Liu (Arabian Journal of Geosciences, 2021)

Crystal Structure, Thermal Expansivity and High-Temperature Vibrational Spectra on Natural Hydrous Rutile - Sha Wang; Jinhua Zhang; Joseph R. Smyth; Junfeng Zhang; Dan Liu; Xi Zhu; Xiang Wang; Yu Ye (Journal of Earth Science, 2020)

Identification of the Nrf2 in the fathead minnow muscle cell line: role for a regulation in response to H2O2 induced the oxidative stress in fish cell - Xiumei Chen; Qiuju Wang; Zhixin Guo; Yunlong Zhao; Sha Luo; Ting Yu; Dongming Zhang; Guiqin Wang (Fish Physiology and Biochemistry, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

Recurrent Talaromyces marneffei Infection Presenting with Intestinal Obstruction in a Patient with Systemic Lupus Erythematosus - Yu-Kun Zhao; Jing-Ye Liu; Juan-Hua Liu; Sha Lu; Hui-Hui Wu; Di-Qing Luo (Mycopathologia, 2020)

Inhibition of glycolysis ameliorate arthritis in adjuvant arthritis rats by inhibiting synoviocyte activation through AMPK/NF-кB pathway - Ying Wang; Hao Xian; Jiajia Qi; Fang Wei; Xiu Cheng; Sha Li; Qing Wang; Zhaoyang Liu; Yun Yu; Jing Zhou; Xiaojin Sun; Hao Liu; et al. (Inflammation Research, 2020)

Aberrant cerebellar neural activity and cerebro-cerebellar functional connectivity involving executive dysfunction in schizophrenia with primary negative symptoms - Ju Gao; Xiaowei Tang; Congjie Wang; Miao Yu; Weiwei Sha; Xiang Wang; Hongying Zhang; Xiangrong Zhang; Xiaobin Zhang (Brain Imaging and Behavior, 2020)

Insight into effects of organic and inorganic phosphorus speciations on phosphorus removal efficiency in secondary effluent - Qi Xu; Keke Xiao; Hui Wang; Qiongxiang Wu; Sha Liang; Wenbo Yu; Huijie Hou; Bingchuan Liu; Jingping Hu; Jiakuan Yang (Environmental Science and Pollution Research, 2020)

L-type Calcium Channels are Involved in Iron-induced Neurotoxicity in Primary Cultured Ventral Mesencephalon Neurons of Rats - Yu-Yu Xu; Wen-Ping Wan; Sha Zhao; Ze-Gang Ma (Neuroscience Bulletin, 2020)

Failure of Placebo Analgesia Model in Rats with Inflammatory Pain - Xiang-Sha Yin; Jin-Yu Yang; Shuai Cao; Yun Wang (Neuroscience Bulletin, 2020)

Increased risk of herpes zoster infection in patients with inflammatory bowel disease: a meta-analysis of cohort studies - Longui Ning; Rongqiang Liu; Sha Li; Guodong Shan; Haojie Du; Jie Zhang; Wenguo Chen; Fenming Zhang; Jinghua Yu; Guoqiang Xu (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Isoflurane produces antidepressant effects inducing BDNF-TrkB signaling in CUMS mice - Sha-Sha Zhang; Yu-Hua Tian; Song-Jun Jin; Wen-Cheng Wang; Jing-Xin Zhao; Xiao-Ming Si; Li Zhang; Hong Xu; Jing-Yu Jin (Psychopharmacology, 2019)

In-situ High-Temperature XRD and FTIR for Calcite, Dolomite and Magnesite: Anharmonic Contribution to the Thermodynamic Properties - Xiang Wang; Xiaoxiang Xu; Yu Ye; Chao Wang; Dan Liu; Xiaochao Shi; Sha Wang; Xi Zhu (Journal of Earth Science, 2019)

Leaf Senescence can be Induced by Inhibition of Root Respiration - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zhu-yu Gu; Fan-jiang Zeng (Journal of Plant Growth Regulation, 2019)

Rheinic acid ameliorates radiation-induced acute enteritis in rats through PPAR-γ/NF-κB - Haixia Sha; Yu Gu; Weixing Shen; Li Zhang; Fei Qian; Yudong Zhao; Haixiao Li; Ting Zhang; Weimin Lu (Genes & Genomics, 2019)

Roles of eNOS in atherosclerosis treatment - Fen-fang Hong; Xiao-yu Liang; Wei Liu; Sha Lv; Shu-jin He; Hai-bin Kuang; Shu-long Yang (Inflammation Research, 2019)

Protective effect of different forms of nitrogen application on cadmium-induced toxicity in wheat seedlings - Lulu Yu; Xinxia Wang; Xiaoyuan Li; Yi Wang; Houyang Kang; Guangdeng Chen; Xing Fan; Lina Sha; Yonghong Zhou; Jian Zeng (Environmental Science and Pollution Research, 2019)

Neurons in rat orbitofrontal cortex and medial prefrontal cortex exhibit distinct responses in reward and strategy-update in a risk-based decision-making task - Dan-Dan Hong; Wen-Qiang Huang; Ai-Ai Ji; Sha-Sha Yang; Hui Xu; Ke-Yi Sun; Aihua Cao; Wen-Jun Gao; Ning Zhou; Ping Yu (Metabolic Brain Disease, 2019)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

Continuous Waterlogging May Not Facilitate Germinability Maintenance of Sphagnum Spores - Lu Feng; Zhao-Jun Bu; Azim Mallik; Zu-Cheng Wang; Sha-Sha Liu; Yu-Huan Wu (Wetlands, 2017)

Characterization of the sulfur-formation (suf) genes in Synechocystis sp. PCC 6803 under photoautotrophic and heterotrophic growth conditions - Sha-Sha Zang; Hai-Bo Jiang; Wei-Yu Song; Min Chen; Bao-Sheng Qiu (Planta, 2017)

Synthesis, insecticidal activities and structure–activity relationship study of dual chiral sulfilimines - Sha Zhou; Xiangde Meng; Ruyi Jin; Yi Ma; Yongtao Xie; Yu Zhao; Hongjian Song; Lixia Xiong; Zhengming Li (Molecular Diversity, 2017)

Anti-glomerular basement membrane glomerulonephritis with thrombotic microangiopathy: a case report - Xiao-juan Yu; Sha-sha Han; Su-xia Wang; Xiao-yu Jia; Wei-yi Guo; Zhao Cui; Feng Yu; Fu-de Zhou; Ming-hui Zhao (Immunologic Research, 2017)

The implication of salience network abnormalities in young male adult smokers - Yangding Li; Kai Yuan; Yanyan Guan; Jiadong Cheng; Yanzhi Bi; Sha Shi; Ting Xue; Xiaoqi Lu; Wei Qin; Dahua Yu; Jie Tian (Brain Imaging and Behavior, 2017)

Neural correlates of 12-h abstinence-induced craving in young adult smokers: a resting-state study - Yangding Li; Kai Yuan; Yanzhi Bi; Yanyan Guan; Jiadong Cheng; Yajuan Zhang; Sha Shi; Xiaoqi Lu; Dahua Yu; Jie Tian (Brain Imaging and Behavior, 2017)

The complete mitochondrial genome of the monophagous moth Protegira songi (Lepidoptera: Noctuidae) - Guo Xiao-Hui; Cheng Ming-Yang; Hou Ya-Feng; Deng Tuan-Tuan; Zhao Sha; Yu Hai-Li; Xing Lian-Xi (Conservation Genetics Resources, 2017)

The Chlorophyll a Fluorescence Characteristic in Different Types of Leaf Senescence in Alhagi sparsifolia - Gang-Liang Tang; Xiang-Yi Li; Li-Sha Lin; Zhu-Yu Gu; Fan-Jiang Zeng (Journal of Plant Growth Regulation, 2016)

The complete mitochondrial genome of the subterranean termite Reticulitermes flaviceps (Isoptera: Rhinotermitidae) - Sha Zhao; Yu-Lei Dang; Hong-Gui Zhang; Xiao-Hui Guo; Xiao-Hong Su; Lian-Xi Xing (Conservation Genetics Resources, 2016)

Dynamic behaviour of the CO2 bubble in a bubble column bioreactor for microalgal cultivation - Yu-Dong Ding; Sha Zhao; Xun Zhu; Qiang Liao; Qian Fu; Yun Huang (Clean Technologies and Environmental Policy, 2016)

Prescreening, identification and harvesting of microalgae with antibacterial activity - Ang Li; Ling Zhang; Zhen-yu Zhao; Sha-sha Ma; Meng Wang; Ping-huai Liu (Biologia, 2016)

Emergy assessment of three home courtyard agriculture production systems in Tibet Autonomous Region, China - Fa-chun Guan; Zhi-peng Sha; Yu-yang Zhang; Jun-feng Wang; Chao Wang (Journal of Zhejiang University-SCIENCE B, 2016)

The association between the ring finger protein 213 (RNF213) polymorphisms and moyamoya disease susceptibility: a meta-analysis based on case–control studies - Xun-Sha Sun; Jun Wen; Jiao-Xing Li; Rong Lai; Yu-Fang Wang; Hui-Jiao Liu; Wen-Li Sheng (Molecular Genetics and Genomics, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Intra-regional and inter-regional abnormalities and cognitive control deficits in young adult smokers - Dan Feng; Kai Yuan; Yangding Li; Chenxi Cai; Junsen Yin; Yanzhi Bi; Jiadong Cheng; Yanyan Guan; Sha Shi; Dahua Yu; Chenwang Jin; Xiaoqi Lu; et al. (Brain Imaging and Behavior, 2016)

Inhibition control impairments in adolescent smokers: electrophysiological evidence from a Go/NoGo study - Junsen Yin; Kai Yuan; Dan Feng; Jiadong Cheng; Yangding Li; Chenxi Cai; Yanzhi Bi; Shi Sha; Xiaomin Shen; Ben Zhang; Ting Xue; Wei Qin; et al. (Brain Imaging and Behavior, 2016)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

Molecular cloning of HMW glutenin subunits from Roegneria kamoji (Poaceae: Triticeae) - Ying-Xia Lei; Kuai Yu; Yi Wang; Xing Fan; Hou-Yang Kang; Li-Na Sha; Yong-Hong Zhou; Hai-Qin Zhang (Biologia, 2016)

Seismic Anisotropy Determined by Shear-Wave Splitting Beneath the Eastern Tibetan Plateau - Sha Liu; Jiansi Yang; Baofeng Tian; Yu Zheng (Pure and Applied Geophysics, 2016)

Risk analysis and emergency actions for Hongshiyan barrier lake - Xingbo Zhou; Zuyu Chen; Shu Yu; Lin Wang; Gang Deng; Peijun Sha; Shouyi Li (Natural Hazards, 2015)

Associations of hypoxia inducible factor-1α gene polymorphisms with susceptibility to digestive tract cancers: a case–control study and meta-analysis - Zhi-Hai Ni; Xian-Jun Liang; Jing-Gang Mo; Yi Zhang; Jian-Hua Liang; Yu-Sha Yang; Yong Zhou; Zhao-Hua Li; Jian-Liang Zhang; Yin-Lu Ding; Peng Zhang; Jin-Qing Wang (Genes & Genomics, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Analysis of the Drought Stress-Responsive Transcriptome of Black Cottonwood (Populus trichocarpa) Using Deep RNA Sequencing - Sha Tang; Yan Dong; Dan Liang; Zhoujia Zhang; Chu-Yu Ye; Peng Shuai; Xiao Han; Ying Zhao; Weilun Yin; Xinli Xia (Plant Molecular Biology Reporter, 2015)

Genetic detection of clubroot resistance loci in a new population of Brassica rapa - Wenxing Pang; Shan Liang; Xiaonan Li; Pengpeng Li; Sha Yu; Yong Pyo Lim; Zhongyun Piao (Horticulture, Environment, and Biotechnology, 2014)

The altitudinal belts of subalpine virgin forest on Mt. Gongga simulated by a succession model - Gen-wei Cheng; Jian Sun; Yu-kun Sha; Ji-hui Fan (Journal of Mountain Science, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Markers associated with altitude and ecological factors in hexaploid Campeiostachys nutans (Griseb.) J. L. Yang, B. R. Baum et C. Yen and tetraploid Roegeneria nutans (Keng) Keng - Yu-Xia Guo; Cheng-Zhang Wang; Xue-Bing Yan; Rui-Yong Wang; Sha-Sha Liu; Miao Tian (Genetic Resources and Crop Evolution, 2014)

Oldest zircon xenocryst (4.17 Ga) from the North China Craton - Pei-Long Cui; Jing-Gui Sun; De-Ming Sha; Xi-Jing Wang; Peng Zhang; A-Lei Gu; Zhong-Yu Wang (International Geology Review, 2013)

Incubation of sperm heads impairs fertilization and early embryo development following intracytoplasmic sperm injection (ICSI) by decreasing oocyte activation in mice - Hui Long; Sheng-Sheng Lu; Yan-Ping Kuang; Zhi-Guang Yan; Hong-Xing Liang; Sha Yu; Wei-Ran Chai; Zheng Yan; Qi-Feng Lyu (Biotechnology Letters, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Short Peptide Segment and Insulin Co-Assembly Forms Cytotoxic Oligomers - Jie Mao; Mei-Sha Chen; Yong-Xiang Chen; Yu-Fen Zhao; Yan-Mei Li (International Journal of Peptide Research and Therapeutics, 2013)

Excision repair of BPDE-adducts in human lymphocytes: diminished capacity associated with ERCC1 C8092A (rs3212986) polymorphism - Tao Yu; Yanhua Liu; Xiaobo Lu; Sha Xiao; Yuan Cai; Cuihong Jin; Qiufang Liu; Jinghua Yang; Shengwen Wu; Xiaoyan Bao; Liang Pan; Tahar van der Straaten (Archives of Toxicology, 2013)

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis - Shu-tao Li; Meng Zhang; Chun-hua Fu; Sha Xie; Yu Zhang; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Enhancing Taxol Biosynthesis by Overexpressing a 9-Cis-Epoxycarotenoid Dioxygenase Gene in Transgenic Cell Lines of Taxus chinensis - Shu-tao Li; Chun-hua Fu; Meng Zhang; Yu Zhang; Sha Xie; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

The unsaturation of phosphatidylglycerol in thylakoid membrane alleviates PSII photoinhibition under chilling stress - Xiao-lin Sun; Sha Yang; Li-Yan Wang; Qiu-Yu Zhang; Shi-Jie Zhao; Qing-Wei Meng (Plant Cell Reports, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Intracellular Delivery of Mitomycin C with Targeted Polysaccharide Conjugates Against Multidrug Resistance - Yu Cao; Didi Chen; Peiguang Zhao; Lina Liu; Xueying Huang; Chao Qi; Yanli Liu; Hongxuan He; Qian Wang; Yang Liu; Sha Chen (Annals of Biomedical Engineering, 2011)

Promoter Analysis of Mouse Scn3a Gene and Regulation of the Promoter Activity by GC Box and CpG Methylation - Guang-Fei Deng; Jia-Ming Qin; Xun-Sha Sun; Zu-Ying Kuang; Tao Su; Qi-Hua Zhao; Yi-Wu Shi; Xiao-Rong Liu; Mei-Juan Yu; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Journal of Molecular Neuroscience, 2011)

Development and characterization of wheat-Psathyrostachys huashanica partial amphiploids for resistance to stripe rust - Yi Wang; Quan Xie; Kangyu Yu; Vaino Poysa; Lijuan Lin; Houyang Kang; Xing Fan; Lina Sha; Haiqin Zhang; Yonghong Zhou (Biotechnology Letters, 2011)

Nitrogen fixation of epiphytic plants enwrapping trees in Ailao Mountain cloud forests, Yunnan, China - Bin Han; Xiaoming Zou; Jijun Kong; Liqing Sha; Hede Gong; Zhen Yu; Tong Cao (Protoplasma, 2010)

Mechanism of the Specific Neuronal Toxicity of a Type I Ribosome-Inactivating Protein, Trichosanthin - Ou Sha; David Tai-Wai Yew; Eric Yu-Pang Cho; Tzi-Bun Ng; Lin Yuan; Wing-Hang Kwong (Neurotoxicity Research, 2010)

Lack of association between ADRA2B -4825 gene insertion/deletion polymorphism and migraine in Chinese Han population - Jian-Qiang Ni; Sha-Sha Jia; Min Liu; Shou-Gong Chen; Yu-Ting Jiang; Wan-Li Dong; Yu-Zhen Gao (Neuroscience Bulletin, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

Inhibition on Hepatitis B virus in vitro of recombinant MAP30 from bitter melon - Jian Ming Fan; Qiao Zhang; Jun Xu; Sha Zhu; Tao Ke; De Fu Gao; Yu Bao Xu (Molecular Biology Reports, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Depressive-like behavior in mice recently recovered from motor disorders after 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Sha Ma; Wei Zhou; Zheng Wei; Yu-Xiang Zheng; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2008)

Molecular identification and the complete nucleotide sequence of TYLCV isolate from Shanghai of China - Zhang Yongping; Zhu Weimin; Cui Huimei; Qiu Yang; Sha Kun; Wan Yanhui; Zhu Longying; Yu Li; Hui Zhang (Virus Genes, 2008)

Using a hybrid fuzzy classifier (HFC) to map typical grassland vegetation in Xilin River Basin, Inner Mongolia, China - Z. Sha; Y. Bai; Y. Xie; M. Yu; L. Zhang (International Journal of Remote Sensing, 2008)

Characterization of on-road CO, HC and NO emissions for petrol vehicle fleet in China city - Hui Guo; Qing-yu Zhang; Yao Shi; Da-hui Wang; Shu-ying Ding; Sha-sha Yan (Journal of Zhejiang University-SCIENCE B, 2006)